Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Mémoires d'une bataille inachevée : la lutte pour l'avortement au Québec, 1970-1992 - Desmarais, Louise (Histoire. Collection Art. 35, 1999)
Chronique des événements entourant la lutte pour l'avortement libre et gratuit, l'une des plus importantes revendications du mouvement féministe québécois. Les différents groupes qui ont mené le combat, leurs discours et la place de leurs actions dans la dynamique des relations qu'ils entretenaient avec les gouvernements et le mouvement anti-avortement. Etude appuyée sur une solide documentation.
Keywords: 1800-1899; 1900-1999; amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; histoire des femmes*; histoire et politique; justice reproductive; militance; patriarcat; périodes historiques; québec; régions géographiques; systèmes d'oppressions; thématiques

Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative

Le mariage des homosexuels : politique comparee des normes franco-americaines - Fassin, E. (FRENCH POLITICS AND SOCIETY, 1999)
Keywords: analyse comparée; cours; his4860; histoire et politique; premier cycle; régions géographiques; thématiques

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Cet article présente, à la lumière des développements récents de l'historiographie féministe, une nouvelle interprétation de la Fédération nationale Saint-Jean-Baptiste. Cette réinterprétation se base sur un concept assez nouveau: le maternalisme, défini comme une catégorie d'analyse utilisée pour qualifier les mouvements de femmes chez qui la maternité constituait le point central de l'idéologie et de l'argumentation. Nous examinons, entre autres, le modèle féminin véhiculé par la FNSJB pour constater qu'il correspondait au modèle traditionnel de « la femme », celui qui effectuait une équation entre la femme et la mère. La maternité n'était toutefois pas perçue par la FNSJB comme une fonction limitative, mais bien comme une ouverture vers la société. Elle a donc dû redéfinir les frontières entre les sphères privée et publique pour permettre aux femmes de transgresser celles du foyer et faire bénéficier la société de leur influence maternelle. Le cadre d'analyse élaboré dans la première partie est ensuite appliqué à un cas concret de revendication: la bataille pour le vote des femmes.
Keywords: 1900-1909; 1900-1999; 1910-1919; amériques; approches et analyses; canada; changement social; corps; cours; droit de vote; fem1000; histoire des femmes*; histoire et politique; maternité; militance; mouvements féministes; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Femmes du siècle - Institut de recherches et d'études féministes (FéminÉtudes, 1999)
Cette publication de 1999 porte sur l’histoire des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; discipline; féminétudes; histoire; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; thématiques

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

Repenser l’État: Nouvelles perspectives féministes - Masson, Dominique (Recherches féministes, 1999)
Depuis déjà une dizaine d'années, les limites des théories féministes classiques sur l'État sont soulignées par de nouvelles perspectives féministes. Leurs reconceptualisations offrent une voie médiane entre le volontarisme des approches libérales et le déterminisme des conceptions plus structurelles. Ancrées dans les notions de luttes politiques et de rapports de forces, celles-ci réorientent l'analyse de «l'État » vers celle de la spécificité des formes étatiques. Elles redonnent également aux luttes des femmes et aux processus de représentation politique une portée analytique et stratégique de même qu'elles permettent une meilleure prise sur la relation entre l'État et l'action politique des femmes.
Keywords: cours; discipline; histoire et politique; pol4102; pol5480; premier cycle; ressource en ligne; science politique; science politique et droit; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Re visions, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; cours; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; sofia; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales

Femmes au miroir: une histoire de l'autoportrait féminin - Borzello, Frances (Thames & Hudson, 1998)
Une sélection d'autoportraits féminins empruntés à toute l'histoire de l'art, de la religieuse anonyme qui glissa son effigie dans la lettrine d'un manuscrit du XIIe siècle à Cindy Sherman et ses photogrammes révélateurs des visions stéréotypées de la femme, en passant par Sofonisba Anguissola, Artemisia Gentileschi, Elisabeth Vigée-Lebrun, Frida Kahlo, Hannah Wilke, etc.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Essentialism vs. social constructionism in the study of human sexuality - DeLamater, John D.; Hyde, Janet Shibley (The Journal of Sex Research, 1998)
According to classical essentialism, there are underlying true forms or essences, there is discontinuity between different forms rather than continuous variation, and these true forms are constant over time. Modern essentialism consists of a belief that certain phenomena are natural, inevitable, and biologically determined. We consider sociobiology, evolutionary psychology, genetic research, brain research, and endocrine research as examples of essentialist approaches, focusing particularly on how these research approaches treat sexual orientation and sexual attraction. Social constructionism, in contrast, rests on the belief that reality is socially constructed and emphasizes language as an important means by which we interpret experience. We briefly review social constructionist research on sexual orientation and sexual attraction. Finally, we review examples of conjoint or interactionist research, uniting biological and social influences. We conclude that, although there may be theories and research that conjoin biological and social influences, there can be no true conjoining of essentialism and social constructionism.
Keywords: approches et analyses; comparaison; construction sociale; cours; discipline; essentialisme; histoire et politique; méthodologie; postmodernisme; premier cycle; sciences humaines; sex2283; sociologie; thématiques

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (Des hommes et des femmes en changement, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Le projet féministe à l’aube du XXIe siècle : un projet de libération et de solidarité qui fait toujours sens - Descarries, Francine (Cahiers de recherche sociologique, 1998)
En situant les rapports de genre au cœur de leur élaboration conceptuelle et en inscrivant leur transformation comme un enjeu stratégique, les études féministes se sont progressivement imposées dans l'univers des sciences humaines comme une approche critique et comme une problématique du changement. Après une revue des trois grands courants de pensée qui se sont développés au sein et en marge du mouvement féministe au cours des dernières décennies, l'auteure se demande si la pensée féministe, ou plutôt les différents courants de la pensée féministe actuelle sont encore engagés dans ces mêmes fins. Sont-elles encore capables de contribuer au renouvellement des savoirs, de proposer un projet de société original, et d'imaginer les termes d'un nouveau contrat entre les genres ? Sont-elles capables de nourrir une lutte féministe unie, une politique de coalition ouverte à la diversité et à la différence, mais qui ne perd rien de sa cohésion et de sa force de ralliement ? Ces questions servent de pistes thématiques pour la discussion de l'auteur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; fem1000; féminisme matérialiste; histoire et politique; justice sociale; militance; mouvements des femmes*; mouvements féministes; occident; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; thématiques

Politiques de l'histoire: Gay New York et l'historiographie homosexuelle aux États-Unis - Fassin, Éric (Actes de la recherche en sciences sociales, 1998)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques; états-unis

Colonialism/postcolonialism - Loomba, Ania (Routledge, 1998)
Colonialism/Postcolonialism est un guide complet mais accessible sur les dimensions historiques, théoriques et politiques des études coloniales et postcoloniales. Ania Loomba examines the key features of the ideologies and history of colonialism, and the relationship of colonial discourse to literature. She goes on to consider the challenges to colonialism, surveying anti-colonial discourses, and recent developments in postcolonial theories and histories. Looking at how sexuality is figured in the texts of colonialism, Colonialism/Postcolonialism shows how contemporary feminist ideas and concepts intersect with those of postcolonialist thought
Keywords: approches et analyses; arts; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; ressource en ligne; thématiques; études littéraires

Écoféminisme - Mies, Maria; Shiva, Vandana (L'Harmattan, 1998)
Est-il possible de créer un nouvel internationalisme, sous la bannière du féminisme et de l'écologie ? La quête d'identité et de différence peut-elle être une plate-forme de résistance à la violence de la mondialisation de l'économie ? Deux femmes, confrontées aux mêmes questions fondamentales sur le sort des générations futures et de la survie de notre planète, l'une avec le regard venant du Sud, l'autre vivant " au cœur de la bête " dans le Nord, se démarquent radicalement de la pensée unique.
Keywords: approches et analyses; com5170; cours; fem1000; histoire et politique; pouvoir; pratiques féministes; premier cycle; ressource en ligne; thématiques; écoféminisme

Le regard de l'autre: artistes canadiens blancs -- sujets féminins noirs = Through an-other's eyes : white Canadian artists -- black female subjects - Nelson, Charmaine; Robert McLaughlin Gallery (Robert McLaughlin Gallery, 1998)
Catalogue d'une exposition tenue du 11 février au 11 avril 1999 à la Robert McLaughlin Gallery, Oshawa, Ont., du 18 juin au 15 août 1999 à la Thames Art Gallery, Chatam, Ont., du 11 janvier au 13 février 2000 à la Galerie d'art Leonard et Bina Ellen, Université Concordia, Montréal et du 16 septembre au 19 novembre 2000 à la Art Gallery of Nova Scotia, Halifax, N.-É.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; féminisme afroaméricain; har4610; histoire et politique; premier cycle; représentation des femme*; représentation des femmes* racisées; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Vieillir homosexuel(le) - Roy, Sophie réalisatrice (Productions Roch Brunette, 1998)
Témoignages de deux aîné.e.s qui ont grandi à l'époque où l'homosexualité n'était pas du tout acceptée dans la société québécoise. Jude est âgé de 62 ans; il est fier, honnête, sensible, homosexuel et sidéen. Infirmière à la retraite, Muriel, 61 ans, vit seule; elle est lesbienne, préfère la liberté et s'intéresse beaucoup à la littérature.
Keywords: amériques; approches et analyses; histoire et politique; hétérosexisme; identités LGBTQIA2+; québec; régions géographiques; sexualité; systèmes d'oppressions; thématiques; témoignage

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

À quoi peut servir l'imagination : Olympe de Gouges et la Révolution française - Scott, Joan Wallach (La citoyenne paradoxale : les féministes françaises et les droits de l'homme, 1998)
Analyse d'un autre paradoxe à la française : le modèle républicain fondé sur l'égalité et la liberté de la personne, mise au service de l'exclusion politique des femmes, qui n'ont obtenu le droit de vote qu'en 1944. Ce livre traite de la protestation féministe contre cette prétendue universalité des droits, qui excluait les femmes de la citoyenneté.
Keywords: 1700-1799; citoyenneté; cours; discipline; droits des femmes*; europe; fem1000; france; histoire; histoire et politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."--BOOK JACKET.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

Histoire comparee de l'homosexualite en Allemagne, en Angleterre et en France dans I'entre-deux guerres - Tarnagne, F. (ACTES DE LA RECHERCHE EN SCIENCES SOCIALES, 1998)
Keywords: 1900-1999; allemagne; angleterre; cours; discipline; entre-deux guerres; europe; france; his4860; histoire; histoire et politique; homosexualité; premier cycle; première guerre mondiale; royaume-uni; régions géographiques; sciences humaines; seconde guerre mondiale; sexualité; sexualités dissidentes; thématiques

Les courants de pensée féministe - Toupin, Louise (L’R des centres de femmes du Québec, 1998)
Les courants de pensée féministe Dans ce document - aussi offert en format PDF - Louise Toupin met en évidence trois grandes traditions de pensée féministe qui sont autant de points de repères qui aident à comprendre l’évolution des diverses tendances féministes. Elle décrit les traditions du féminisme libéral, du féminisme marxiste et du féminisme radical et traite des métamorphoses qu’elles ont connues ainsi que des perspectives nouvelles qui les ont traversées.
Keywords: 1900-1999; cours; discipline; fem1000; histoire et politique; mouvements féministes; occident; premier cycle; périodes historiques; ressource en ligne; sciences humaines; sex3383; sofia; thématiques; théories féministes

Présentation : du fléau social au fait social. L’étude des homosexualités - Chamberland, Line (Sociologie et sociétés, 1997)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; homosexualité; identités LGBTQIA2+; militance; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1183; sexualité; soc2014; sociologie; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

L'histoire des femmes : construction et déconstruction d'une mémoire sociale - Fahmy-Eid, Nadia (Sociologie et sociétés, 1997)
Cet article analyse le rapport entre la mémoire sociale des femmes et l'histoire féministe qui a vu le jour au cours des trente dernières années. L'hypothèse défendue ici est que mémoire et histoire s'alimentent réciproquement et qu'elles sont toutes deux le fruit d'un construit social. Toutes deux opèrent un tri dans le passé et l'ordonnent selon une perspective particulière. Toutes deux s'inscrivent dans des rapports de pouvoir, rapports qu'elles reflètent en partie, mais qu'elles contribuent également à interroger et à remettre en cause. C'est ainsi que la mémoire des femmes et l'histoire féministe se sont avérées des éléments importants de conscientisation et de changement social.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; mémoire culturelle; pratiques féministes; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

Une revue à soi - Institut de recherches et d'études féministes (FéminÉtudes, 1997)
Cette publication de 1997 porte sur l’héritage du lieu à soi de Virginia Woolf. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; féminétudes; histoire et politique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)
Keywords: 1900-1999; DIG; amériques; art; discipline; femmes* artistes; histoire des femmes*; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Des mots, des pratiques et des risques : la gestion différenciée de la parole et de la prévention du VIH chez des hommes à comportements bisexuels en France - Mendès-Leite, Rommel; Deschamps, Catherine (Sociologie et sociétés, 1997)
Cet article présente une partie des résultats de deux recherches socio-anthropologiques réalisées en France auprès d'hommes ayant des rapports sexuels avec des hommes et des femmes, indépendamment de leur identité socio-sexuelle. Les analyses portent d'abord sur les perceptions différenciées de la sexualité et sur ses conséquences en matière de restitution du sens, et ensuite sur la gestion des comportements préventifs. Ainsi il apparat!, au travers d'une relecture des notions de " multipartenariat ", de " sexe occasionnel " ou de " fidélité ", que le principal lieu de rupture dans la gestion des risques vin est avant tout dépendant de la variable sexe des partenaires sexuels, quand bien même la compréhension de ce mécanisme ne se réduit pas à une opposition basique entre hommes et femmes.
Keywords: 1900-1999; VIH; analyse différenciée selon les sexes -ADS+; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire et politique; hétérosexisme; justice sociale; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité masculine; sociologie; systèmes d'oppressions; thématiques

Histoires de silence et de répression - Núñez, Fefa Vila; Llamas, Ricardo (Nouvelles Questions Féministes, 1997)
Le développement du mouvement de lesbiennes et de gays en Espagne commence dans les années soixante-dix par une remise en cause des lois répressives du régime franquiste — qui visaient surtout les hommes. Après avoir brièvement lutté avec les homosexuels, les lesbiennes rejoignent le mouvement féministe. Les années quatre-vingt sont celles des débats théoriques et d'un certain émiettement du mouvement. A la fois rendues invisibles par le système, objets de violences spécifiques et de tentatives de récupération, une partie des lesbiennes s'orientent à partir des années quatre-vingt dix vers une nouvelle alliance avec les gays, autour de la lutte contre le SIDA. Ce retour à une certaine mixité — consciente des différences d'intérêts entre gays et lesbiennes — est liée à une revendication joyeuse du corps et de la visibilité dans une perspective "queer".
Keywords: espagne; europe; histoire et politique; identités LGBTQIA2+; militance; personnes lesbiennes; ressource en ligne; régions géographiques; thématiques

Le Red light de Montréal - Proulx, Daniel (Études québécoises, 1997)
"La légende du défunt quartier montréalais dit du "Red Light" vaut bien celle des Soho et Pigalle de ce monde. Prospères au début du siècle, les salles de jeux enfumées et les chambres sordides de nos bas-fonds deviennent dans les années trente les derniers refuges des damnés de la crise. La guerre venue, les entrepreneurs en plaisirs défendus font des affaires d'or, en attendant que l'armée s'en mêle. La guerre finie, le Red Light renaît en force. C'est alors que Pacifique Plante et Jean Drapeau entrent en scène et procèdent à l'épuration radicale de nos moeurs. Le rideau tombe sur notre quartier "réservé". Aujourd'hui, la "Main" n'est plus qu'un coin de rue, à l'intersection de Sainte-Catherine et de Saint-Laurent. Ni ses habitués ni les passants n'ont idée de son spectaculaire passé." -- Quatrième de couverture
Keywords: 1900-1999; amériques; canada; cours; discipline; his4860; histoire; histoire de la sexualité; histoire et politique; industrie du sexe; montréal; premier cycle; périodes historiques; québec; red light; régions géographiques; révolution tranquille; sciences humaines; sexualité; thématiques; travail; travail du sexe

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Ideología argentina (Universidad Nacional de Quilmes), 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires

Mémoires lesbiennes : le lesbianisme à Montréal entre 1950 et 1972 - Chamberland, Line (De mémoire de femmes, 1996)
Line Chamberland retrace la vie de femmes qui ont eu le courage de leurs amours à une époque où la condamnation sociale du lesbianisme était unanime. À partir de nombreux témoignages, l’auteure démontre de quelle façon s’exerçait le contrôle social du lesbianisme, quel rôle jouait la famille et comment diverses instances comme les institutions religieuses, l’appareil judiciaire et les autorités psychomédicales veillaient à ce que ces femmes se conforment aux diktats, les poussant parfois à la marginalité ou les obligeant à adopter diverses stratégies de dissimulation.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; violences

Science, conscience et action : vingt-cinq ans de recherche féministe au Québec - Dagenais, Huguette (Les éditions du remue-ménage, 1996)
Après un quart de siècle de néoféminisme, on connaît encore mal la recherche féministe et l’ampleur du travail accompli par ces chercheuses. Les auteures examinent ici les travaux qui ont porté sur la famille, la conciliation travail-famille et sur l’emploi, ceux qui ont documenté des aspects particuliers de la santé des femmes et de la violence conjugale ainsi que les nombreuses études produites dans le domaine de l’éducation. Elles mettent également en lumière les changements et les résistances révélés par les recherches dans le champ religieux, le champ politique, celui du droit de même que dans le domaine des communications. Ce faisant, elles rendent manifestes les caractéristiques de la recherche féministe québécoise, notamment les liens établis par les chercheuses entre théorie et pratique, recherche et action. Des textes de Pierrette Bouchard, Anita Caron, Renée Cloutier, Christine Corbeil, Huguette Dagenais, René B.-Dandurand, Francine Descarries, Louise Guyon, Thérèse Hamel, Geneviève Martin, Karen Messing, Josée Néron, Ann Robinson, Armande Saint-Jean, Diane-Gabrielle Tremblay et Manon Tremblay.
Keywords: 1900-1999; amériques; conciliation famille-travail; cours; discipline; droit; famille; fem1000; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; santé; science des religions; science politique; science politique et droit; sciences humaines; thématiques; théologie; violences; violences contre les femmes*

The cultural contradictions of motherhood - Hays, Sharon (Yale University Press, 1996)
Les mères qui travaillent sont aujourd’hui confrontées à des exigences contradictoires en termes de temps et d’énergie, mais aussi à des idées contradictoires sur la manière dont elles doivent se comporter : elles doivent être attentionnées et altruistes lorsqu’elles s’occupent de leurs enfants, mais compétitives et ambitieuses au travail. Alors que de plus en plus de femmes entrent sur le marché du travail, il semblerait raisonnable que la société fasse de la maternité une tâche plus simple et plus efficace. Au lieu de cela, Sharon Hays souligne dans ce livre original et provocateur qu’une idéologie de « maternité intensive » s’est développée, qui ne fait qu’exacerber les tensions auxquelles les mères qui travaillent sont confrontées. S’appuyant sur des idées sur la maternité depuis le Moyen Âge, sur des manuels contemporains d’éducation des enfants et sur des entretiens approfondis avec des mères de diverses classes sociales, Hays retrace l’évolution de l’idéologie de la maternité intensive – une idéologie qui tient la mère pour principale responsable de l’éducation des enfants et qui impose que le processus soit centré sur l’enfant, guidé par des experts, absorbant émotionnellement, exigeant en main-d’œuvre et coûteux financièrement. Hays soutient que ces idées sur la maternité appropriée découlent d’une ambivalence fondamentale à l’égard d’un système fondé uniquement sur la poursuite compétitive d’intérêts individuels. En essayant de faire face à notre profond malaise face à l’intérêt personnel, nous avons imposé des obligations et des engagements irréalistes et non rémunérés à la maternité, la transformant en une force opposée, un terrain privilégié sur lequel cette ambivalence culturelle se joue.
Keywords: approches et analyses; capitalisme; discipline; histoire et politique; individualisme; maternité; maternité intensive; projet charge mentale; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Terre(s) des femmes? - Institut de recherches et d'études féministes (FéminÉtudes, 1996)
Cette publication de 1996 aborde les identités et les théories postmodernes de la fin du XXe siècle en études féministes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; droits des femmes*; féminétudes; histoire et politique; intersectionnalité; militance; postmodernisme; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Le Rose et le noir : les homosexuels en France depuis 1968 - Martel, Frédéric (Epreuve des faits, 1996)
"Ce livre est une chronique des homosexuels en France, hommes et femmes, depuis 1968. L’homosexualité est un fil rouge qui relie entre eux des phénomènes majeurs : libération sexuelle, féminisme, mutation des modes de vie, lutte contre le sida, pacs… Frédéric Martel évoque les figures emblématiques et les activistes, mais aussi les débats et les combats, tout ce qui a contribué à ce que les « gais » sortent de l’ombre. Plus visibles, mieux acceptés, les homosexuels sont aujourd’hui en quête de reconnaissance." -- Site de l'éditeur
Keywords: 1900-1999; LGBTQIA2+; activisme; approches et analyses; cours; discipline; discours militant; droits des femmes*; europe; france; his4860; histoire du féminisme; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; lesbianisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

La construction du "French Feminism" dans le discours universitaire américain - Moses, Claire (Nouvelles Questions Féministes, 1996)
Les chercheuses en études féministes aux Etats-Unis ont publié de nombreux articles sur le féminisme français; pourtant, peu de féministes françaises s'y reconnaissent ou y reconnaissent leur mouvement. Cet article porte sur la disjonction qui existe entre la version américaine du féminisme français et le mouvement dont la pratique et la théorie ont eu un impact sur la politique, la culture, et la société françaises des vingt dernières années. Cet article part du principe que la version américaine n'est pas simplement une interprétation erronée des faits. Bien que je décrive très brièvement le modèle que les militantes et les critiques féministes ont élaboré, ma contribution porte plus sur l'organisation de la connaissance aux Etats-Unis et l'impact de la recherche féministe américaine sur le mouvement français. Dans le modèle américain du féminisme français, les théoriciennes Hélène Cixous, Julia Kristeva, et Luce Irigaray, ainsi que le groupe Psychanalyse et Politique sont pris comme modèles. Le militantisme s'efface devant la théorie, les théories matérialistes devant le post-structuralisme, la dimension sociale et historique devant le discours littéraire et philosophique. Pourquoi en est-il ainsi? Quels a priori politiques se cachent derrière la version américaine du féminisme français? Cet article a pour objectif d'avancer quelques réponses et de soulever plus encore de questions. Ce faisant, j'espère mettre à jour la diversité des engagements politiques conflictuels qui façonnent la recherche intellectuelle aux Etats-Unis et montrer les conséquences variées et pas toujours voulues de celle-ci. Much has been written in U.S. feminist scholarship about "French feminism", but few French feminists recognize themselves or their movement in these studies. This article looks at this disjunctive between the American version of "French feminism" and the movement whose practice and theory had an impact on French politics, culture, and society over the past two decades. The premise of the article is that the disjunctive is not simply a matter of "getting the story wrong". Although I describe (very briefly) the movement that feminist activists and scholars have constructed for themselves, the interest of this paper is more so on the construction of knowledge in the U.S. and the impact of U.S. feminist scholarship on the French movement. In the American construction of "French feminism", theorists Hélène Cixous, Julia Kristeva, and Luce Irigaray, along with the group Psychanalyse et politique, are the significant exemplars. Theory is privileged over activism, poststructuralism over materialist theories, literary and philosophical discourse over the social and historical. Why? What political assumptions are embedded in the U.S. construction of "French feminism'"? This paper intends to offer some answers (and raise many more). In so doing, I hope to make clear the variety of conflicting political agendas that inform U.S. intellectual work and the variety of consequences, not always intended, that this work has had.
Keywords: 1900-1999; amériques; cours; débat; europe; fem1000; france; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Feminist theorists: Three centuries of women's intellectual traditions - Spender, Dale (Women's Press, 1996)
Feminism was not born in 1968. Yet the work of three centuries of feminist thinkers has been dismissed, distorted or forgotten. Even the names of many of them remain unfamiliar, and few have so much as a mention in history books. Feminist Theorists demonstrates once and for all that we can no longer be content with received ideas about 'progress', which may explain the world for men, but which fail to make sense of the historical experience of women. It shows too that contemporary women have a rich intellectual tradition on which to draw for stimulus, inspiration and enjoyment.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire et politique; justice sociale; mouvements féministes; premier cycle; sciences humaines; thématiques; théories féministes

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

The new lesbian studies: Into the twenty-first century - Zimmerman, Bonnie; McNaron, Toni A. H. (Feminist Press at the City University of New York, 1996)
Foreword by Margaret Cruikshank Introduction by Bonnie Zimmerman and Toni A. H. McNaron By celebrating the differences among lesbian scholars and attending to the ways in which the field has been shaped by shifting politics and the emergence of queer studies, this collection challenges the limits of lesbian studies while affirming its value. Forty essays arranged in six parts explore the history of lesbian studies as well as its current impact on conceptions of identity and community, teaching, academic disciplines, university practices, and the development of feminist and queer theories. The collection offers stirring personal testimony; multicultural and international perspectives and established and new voices; strategies for integrating lesbian studies into the curriculum; and contributions from lesbians working in libraries, athletic departments, and students services. Throughout, the contributors address the ways in which lesbian studies has transformed and will continue to transform traditional disciplines, practices, and thought.
Keywords: approches et analyses; histoire et politique; lesbianisme; personnes lesbiennes; queer; thématiques

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics--such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha--in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

A diplomacy of the oppressed: New directions in international feminism - Ashworth, Georgina (Zed Books, 1995)
Les contributrices abordent les problèmes du mouvement international des femmes, tels que la résolution des conflits; la violence; zones de libre-échange ; l'environnement; culture et identité nationale; santé; les média; droits humains; et l'emploi, en mettant l'accent sur la situation des femmes dans toutes les régions du monde. Destiné aux étudiants en études féministes, en sciences politiques et en études du développement
Keywords: 1900-1999; anthologie; approches et analyses; conflit; coopérative internationale; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; inégalités; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Opus, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Fémininmasculin: le sexe de l'art. - Centre Georges Pompidou. (Passage du siècle, 1995)
Premier chapitre du Passage du siècle (les grands bilans que le Centre Georges Pompidou proposera en 1996 et 1997), cette exposition renoue avec des expériences décisives comme par exemple "Eros", organisée en 1959 par Marcel Duchamp et André Breton. A travers le titre "Féminin - Masculin, le sexe de l'art" s'exprime un double enjeu : celui de réhabiliter le terme dévalué d'une opposition inscrite dans la tradition des couples hiérarchiques de la pensée occidentale (forme/matière, vérité/mensonge, être/paraître, profondeur/surface, etc.) ; celui de montrer qu'au delà d'un simple sujet-motif artistique, le sexe est partie prenante des processus de l'art lui-même. L'ambition de cette exposition est de montrer, en dehors de toute approche chronologique, comment les productions artistiques du XXe siècle n'ont eu de cesse de venir brouiller les fatalités biologiques, anatomiques et culturelles traditionnellement liées au sexe. Aborder l'art dans la perspective de la différence sexuelle, ce n'est pas mécaniquement opposer un art "masculin" à un art "féminin", mais tenter de donner à voir comment les oeuvres se trouvent traversées par cette question, au-delà du sexe - du genre - des artistes qui les produisent. Féminin - Masculin, le sexe de l'art montrera aussi la coexistence dans ce siècle de deux généalogies artistiques concernant le sexe. L'une, à partir de Picasso, s'inscrit dans la tradition classique de la différence des sexes, conçue comme une opposition dialectique et organique du masculin et du féminin. L'autre, à partir de Marcel Duchamp, inaugure un nouveau type de relations, selon une logique asymétrique, faisant circuler les intensités masculines et féminines sur un mode proliférant qui opère une déterritorialisation des entités anatomiques, identificatoires et formelles. Les artistes de la jeune génération (tant américaine qu'européenne) semblent très sensibles à cette manière de déstabiliser les polarités traditionnelles du masculin et du féminin, mettant en oeuvre de nouvelles configurations éthiques et formelles qui se situent au-delà de la différence sexuelle, et en cela se distinguant en radicalement des positions identitaires des années 70.
Keywords: 1900-1999; LGBTQIA2+; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; exposition; har4600; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Moi, Tituba sorcière --: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Littératures et cultures, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

La vague antiféministe - Institut de recherches et d'études féministes (FéminÉtudes, 1995)
Cette publication porte sur la nécessité d’être féministe en 1995 et sur l’histoire de l’antiféminisme à la fin du XXe siècle. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; antiféminisme; approches et analyses; droits des femmes*; féminétudes; histoire et politique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Un sujet inclassable? approches sociologiques, littéraires et juridiques des homosexualités - Mendès-Leite, Rommel (Université, 1995)
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droits; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Bisexuality and the challenge to lesbian politics: Sex, loyalty, and revolution. - Rust, Paula C. (The Cutting Edge: Lesbian Life and Literature Series, 1995)
Le sujet de la bisexualité continue de diviser la communauté lesbienne et gay. Lors des marches des fiertés, dans des films comme Go Fish, lors de conférences universitaires, le rôle et le statut des bisexuels sont âprement contestés. Au sein des communautés lesbiennes, constituées pour soutenir les lesbiennes dans une société patriarcale et hétérosexiste, les femmes bisexuelles sont souvent perçues comme une menace ou comme une faiblesse politique. Les femmes bisexuelles se sentent considérées avec suspicion et méfiance, voire ouvertement méprisées. S'appuyant sur ses recherches auprès de plus de 400 femmes bisexuelles et lesbiennes, sur le traitement de la bisexualité dans la presse lesbienne et gay et sur la croissance récente d'un mouvement bisexuel résolument politique, Paula Rust aborde une série de questions relatives à la politique et relations sociales entre lesbiennes et femmes bisexuelles. En remontant les racines de la controverse sur la bisexualité parmi les lesbiennes aux premiers débats féministes lesbiens des années 1970, Rust soutient que ces débats ont créé les circonstances dans lesquelles la bisexualité est devenue un défi inévitable à la politique lesbienne. Elle le retrace également, prédisant l’avenir de la politique sexuelle.
Keywords: amériques; approches et analyses; bisexualité; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; militance; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; états-unis

Le pouvoir dans les groupes de femmes de la région de Québec - Couillard, Marie-Andrée (Recherches sociographiques, 1994)
Les idéaux féministes d'égalité formulés au cours des années 1970 et 1980 sont aujourd'hui confrontés à des discours divers qui pénètrent les groupes de femmes. D'une part, la vision des technocrates les incite à accepter des fonctions instrumentales en retour d'un financement considéré essentiel par plusieurs. La majorité des groupes en sont ainsi venus à offrir des services qui se situent dans le prolongement de ceux offerts par le réseau de la santé et des services sociaux. À travers ces ajustements, les groupes de femmes ne se définissent plus seulement comme des lieux de conscientisation et de résistance, mais bien comme des groupes communautaires travaillant, de concert avec d'autres groupes communautaires, à l'amélioration du bien-être collectif. Les discours savants portant sur le féminisme, sur les conditions de sa mise en oeuvre ou sur le rapport entre l'État et le communautaire rejoignent eux aussi les militantes et affectent de façons diverses le portrait qu'elles tracent de leurs pratiques. C'est cet ensemble complexe dans lequel des rapports de force se nouent quotidiennement que nous voulons décrire et analyser ici.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; discipline; groupes de femmes; histoire et politique; militance; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Méthodologie féministe pour les femmes et le développement : concepts, contextes et pratiques dans L'égalité devant soi: sexes, rapports sociaux et développement international - Dagenais, Huguette (L'égalité devant soi: sexes, rapports sociaux et développement international, 1994)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; sexisme; système colonial; systèmes d'oppressions; thématiques

Women, feminism, and development - Dagenais, Huguette; Piché, Denise; Institut canadien de recherches sur les femmes Colloque (1988 : Québec, Québec); Université Laval Groupe de recherche et d'échange multidisciplinaires féministes (Published for the Canadian Research Institute for the Advancement of Women by McGill-Queen's University Press = Publié pour l'Institut canadien de recherches sur les femmes par McGill-Queen's University Press, 1994)
Extrait de la couverture : "[Cet ouvrage] illustre l'apport significatif de la perspective féministe aux travaux sur le développement en mettant particulièrement l'accent sur les constributions de chercheuses et d'activistes canadiennes. Ce livre couvre un grand nombre de thèmes et de préoccupations et réunit des auteures oeuvrant dans une grande variété d'organisations et de disciplines. Les chapitres portent sur des aires culturelles et géographiques aussi différentes que la Chine ; la Malaisie et la Thailande ; le Mexique et les Antilles ; l'Ouganda, le Malawi et le Ghana de même que sur les sociétés inuit et indiennes du Canada. Une communauté de vue et un appel à une reconceptualisation du développement émergent de l'ensemble de ces voix."
Keywords: agriculture; approches et analyses; cours; droits des femmes*; développement; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; thématiques; travail

Ces femmes qui ont bâti Montréal : la petite et grande histoire des femmes qui ont marqué la vie de Montréal depuis 350 ans - Darsigny, Maryse; Descarries, Francine; Kurtzman, Lyne; Tardy, Évelyne (Les éditions du remue-ménage, 1994)
Plus de 350 chroniques et illustrations, couvrant l’histoire de Montréal depuis sa fondation, répertoriant des réalisations dans tous les secteurs d’activités, des synthèses et des repères chronologiques précieux sous la plume alerte de plus de 150 collaboratrices: journalistes, historiennes, militantes féministes, chercheures, étudiantes, écrivaines…
Keywords: SAC; amériques; discipline; histoire; histoire des femmes*; histoire et politique; montréal; politique; québec; régions géographiques; sciences humaines; thématiques

A History of Our Own - Eaklor, Vicki L. (The Lesbian Review of Books, 1994)
Lesbians played a role in all phases of Grove development, albeit that of a minority in number and, usually, in terms of power and recognition. Newton devotes two chapters (of eleven) exclusively to lesbians, and this seems adequately proportional to the lesbian presence in the decades she covers. Importantly, the differences for women between the two eras -- 1930s to 1960 and 1960 to 1980 -- appear to be determined by class and ethnicity rather than by gender. In the earlier period, says Newton, the gay "girls" or "ladies" (Grovers' terms) "were an elite, privileged group who faced relatively little cultural exclusion or discrimination from their male peers" (204); and, she reminds us, in both eras "whatever problems 'girls' had with 'boys,' physical safety was not one of them" (204). Although they never completely shared in the camp sensibility, and not at all in the public sex of the "Meat Rack," then, Grove lesbians were on an even footing (except in numbers) as long as they were white, Protestant, moneyed, artistic/theatrical, and devoted to the "fun" ethos of the settlement (indeed, "party" meant costumes and drinking, never politics). At the opposite end of New York State from Buffalo is Cherry Grove, a gay community as different from that treated in Boots of Leather as the geography symbolizes. As Esther Newton describes it in Cherry Grove, Fire Island, it could be a typical "all-American" postwar town -- dominated by the sensibilities of elite WASP males benefiting from the prosperity of the 1950s and 1960s, and hostile at times to those perceived as outsiders (by race, gender, ethnicity) or interlopers (day-trippers, pretentious Pines neighbors). The crucial exception, of course, is that the elitist WASP men (and some women) who built the town were gay. For these reasons, my reactions divided according to my dual identity. As a historian, I found this book superb in every way: it is an engaging narrative of six decades of the area's development textured with insightful commentary on the larger context of American life and questions regarding how and why Cherry Grove originated and endured. However, the lesbian reader in me, although agreeing that the presentation is wonderful (it is actually more fluid and readable than Boots of Leather), reacted to the sexism, racism, anti-Semitism, and classism that have characterized this community at various stages of its existence, and especially to the community's dismissal of women. As Newton herself summarizes in a passage concerning the "invasion" of the neighboring Pines community, "Whatever the Queen's function -- selling tickets to a play or blessing the bathers -- she also is the Grove, its key symbol and core representation" (269; italics in the original); and she adds in the accompanying endnote, "The normal processes of Grove action and narration tend to marginalize or even erase women" (345, n.7)
Keywords: discipline; histoire; histoire et politique; personnes lesbiennes; ressource en ligne; sciences humaines; sexualité; thématiques

Chloe plus Olivia: An anthology of lesbian literature from the seventeenth century to the present - Faderman, Lillian (Viking, 1994)
Dans Chloe Plus Olivia, Lillian Faderman ne cherche rien de moins à redéfinir radicalement quatre siècles de littérature lesbienne, répondant à un besoin longtemps négligé : une anthologie littéraire d'écrivains lesbiens des quatre derniers siècles, chaque pièce étant située dans un contexte historique et littéraire. Cet ouvrage de recherche historique propose une revue éclairante du concept changeant de « littérature lesbienne », suivi d'exemples de six genres différents : l'amitié romantique, l'inversion sexuelle, les lesbiennes exotiques et maléfiques, l'encodage lesbien, le féminisme lesbien et le féminisme post-lesbien. Faderman examine des œuvres aussi diverses que My Antonia de Willa Cather et Orlando de Virginia Woolf ; poésie de Gertrude Stein et Amy Lowell ; fiction de Carson McCullers, Helen Hull et Alice Walker. De plus, Chloe Plus Olivia contient des écrits d'hommes axés sur les relations entre femmes. Ces écrits sont inclus dans la première section du livre et ont été, à divers égards, importants pour le développement de la littérature lesbienne, puisque les hommes étaient beaucoup plus susceptibles que les femmes d'être publiés au cours des autres siècles. Il serait impossible d’identifier une seule « grande tradition » d’écriture lesbienne, car elle est en constante métamorphose, reflétant l’évolution des attitudes sociales et des voix des femmes. Chloe Plus Olivia , avec sa portée historique renforcée par la recherche personnelle de Faderman pour une définition de la littérature lesbienne, en fait le premier livre du genre ; il deviendra certainement le point de référence à partir duquel partiront toutes les études ultérieures sur la littérature lesbienne.
Keywords: arts; discipline; histoire; histoire et politique; littérature; outils; ouvrages de références; personnes lesbiennes; sciences humaines; thématiques; études littéraires

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Femmes : moitié de la terre, moitié du pouvoir - Halimi, Gisèle; femmes (Association), Choisir--la cause des (Gallimard, 1994)
Les 3 et 4 juin 1993, le mouvement Choisir-La cause des femmes, que préside Gisèle Halimi, a organisé au palais de l'Unesco, à Paris, un colloque international pour la parité femmes-hommes dans toutes les instances politiques de notre pays. Ce colloque a rassemblé une soixantaine de personnalités de vingt-deux pays (dont la Chine) parmi lesquelles plus de quarante femmes ministres, anciennes ministres, députées, anciennes députées, ambassadrices, présidentes de Parlements, ainsi que des historiennes, écrivaines, sociologues, politologues, juristes, etc. Ce sont les minutes de ce colloque qui sont ici publiées. La diversité des intervenantes - de Simone Veil à la secrétaire d'État américaine Hazel O'Leary, de la ministre israélienne Shulamith Aloni à la diplomate palestinienne Hanan Ashraoui - réunies pour promouvoir une «autre démocratie» donne à ce livre un caractère exceptionnel qui fera date et marque une nouvelle étape dans le combat des femmes pour la parité qui est aujourd'hui «l'idée neuve en Europe».
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; fem1000; femmes* politiques; histoire et politique; interdisciplinarité; international; inégalités; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; égalité femme*-homme

Fatal women: Lesbian sexuality and the mark of aggression - Hart, Lynda (Princeton University Press, 1994)
Partant du lien historique entre criminalité et déviance sexuelle, Lynda Hart construit une théorie complexe et originale dans laquelle l'ombre de la lesbienne anime les représentations des femmes violentes dans la littérature, les pièces de théâtre, les films et les performances. Les chapitres détaillent cette théorie dans divers domaines, notamment : * Lulu Plays de Frank Wedekind * Thelma and Louise et Basic Instinct * l'art de la performance de Karen Finley dans le contexte des débats sur la censure * La performance des Split Britches, Lesbians Who Kill Fatal Women, est une contribution majeure à la théorie lesbienne et aux études culturelles. C'est une étude stimulante et enrichissante.
Keywords: arts; discipline; histoire et politique; personnes lesbiennes; ressource en ligne; sexualité; thématiques; violences; études culturelles; études littéraires

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp; no. 27; 5, 1994)
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques

The Lesbian and gay studies reader - Abelove, Henry; Barale, Michèle Aina; Halperin, David M. (Routledge, 1993)
Rassemblant quarante-deux essais révolutionnaires, dont beaucoup sont déjà des classiques, The Lesbian and Gay Studies Reader fournit une introduction indispensable à l'état contemporain des études lesbiennes/gay, illustrant largement l'étendue, la portée, la diversité, l'attrait et puissance du travail actuellement réalisé dans le domaine. Présentant des essais d'éminents chercheurs tels que Judith Butler, John D'Emilio, Kobena Mercer, Adrienne Rich, Gayle Rubin et Eve Kosofsky Sedgwick, The Lesbian and Gay Studies Reader explore une multitude d'expériences sexuelles, ethniques, raciales et socio-économiques. . S'étendant sur des disciplines telles que l'histoire, la littérature, la théorie critique, les études culturelles, les études afro-américaines, les études ethniques, la sociologie, l'anthropologie, la psychologie, les classiques et la philosophie, cette anthologie retrace l'inscription des significations sexuelles dans toutes les formes d'expression culturelle. Représentant le meilleur et le plus important travail en langue anglaise dans le domaine, The Lesbian and Gay Studies Reader aborde des sujets tels que les rôles butch-fem, la construction culturelle du genre, le séparatisme lesbien, la théorie féministe, le sida, l'éducation sexuelle sans risque, le colonialisme, le S /M, Oscar Wilde, Gertrude Stein, les livres pour enfants, le nationalisme noir, les films populaires, Susan Sontag, le placard, l'homophobie, Freud, Sappho, les médias, les hijrasde l'Inde, Robert Mapplethorpe, et la politique de représentation. Il contient également un essai bibliographique détaillé qui fournira aux lecteurs un guide inestimable pour des lectures complémentaires. Contributeurs :Henry Abelove, Tomas Almaguer, Ana Maria Alonso, Michele Barale, Judith Butler, Sue-Ellen Case, Danae Clark, Douglas sertissage, Teresa de Lauretis, John D'Emilio, Jonathan Dollimore, Lee Edelman, Marilyn Frye, Charlotte Furth, Marjorie Garber , Stuart Hall, David Halperin, Phillip Brian Harper, Gloria T. Hull, Maria Teresa Koreck, Audre Lorde, Biddy Martin, Deborah E. McDowell, Kobena Mercer, Richard Meyer, DA Miller, Serena Nanda, Esther Newton, Cindy Patton, Adrienne Rich, Gayle Rubin, Joan W. Scott, Daniel L. Selden, Eve Kosofsky Sedgwick, Barbara Smith, Catharine R. Stimpson, Sasha Torres, Martha Vicinus, Simon Watney, Harriet Whitehead, John J. Winkler, Monique Wittig et Yvonne Yarbro -Bejarano
Keywords: approches et analyses; corps; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; outils; ouvrages de références; racisme; santé; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; violences

«Débat». Femmes et histoire : Colloque, La Sorbonne, 13-14 novembre 1992 - Farge, Arlette; Perrot, Michelle (Femmes et histoire : Colloque, La Sorbonne, 13-14 novembre 1992, 1993)
Commencée fin 1987, « L’histoire des femmes en Occident » vient de s’achever. Ce travail collectif international d’une grande ampleur - 5 volumes, 3 000 pages écrites par 72 auteurs - constitue à ce jour l’effort le plus achevé pour affirmer la légitimité d’un champ de recherche : l’approche sexuée de l’histoire de nos sociétés. Publiée en 9 langues, cette entreprise a suscité aussitôt un immense intérêt, signe incontestable d’une demande sociale forte. Mais cette approche historique pose beaucoup de questions : sur la pertinence de la chronologie classique, sur la notion d’Occident et son étroitesse, sur la validité des sources, sur la fonction des images, sur la difficulté à saisir autre chose qu’une représentation construite majoritairement par les hommes, sur le consentement des femmes à leur rôle, sur la notion de pouvoirs, sur celle de progrès... Prolongement critique de « L’histoire des femmes en Occident », le colloque « Femmes et Histoire » est la manifestation d’une réflexion ouverte et actuelle qui ne demande qu’à se poursuivre.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; inégalités; occident; premier cycle; rapports sociaux de sexe; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Les dessous des Folles alliées : un livre affriolant - Godbout, Lucie (Les éditions du remue-ménage, 1993)
Lucie Godbout, ex-Folle alliée, rappelle ici dix ans de théâtre, de cabaret, de shows tous plus drôles les uns que les autres… Un livre aussi vivant que leurs spectacles, des personnages qui interviennent dans le récit et des extraits de leur dernier show, C’est parti mon sushi!
Keywords: 1900-1999; 1980-1989; amériques; discipline; femmes* artistes; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; régions géographiques; thématiques; théâtre; travail

Déclaration des droits de la femme et de la citoyenne - Gouges, Olympe de (Écrits politiques 1788-1791, 1993)
Keywords: 1700-1799; citoyenneté; cours; discipline; droits des femmes*; europe; fem1000; france; histoire; histoire et politique; incontournable; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques

Heavenly love?: Lesbian images in twentieth-century women's writing - Griffin, Gabriele (Manchester University Press, 1993)
Keywords: 1900-1999; arts; discipline; histoire et politique; littérature; personnes lesbiennes; périodes historiques; thématiques; études littéraires

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Une victoire à la Pyrrhus ? : la lutte pour le droit à l’avortement - Lamoureux, Diane (Avortement : pratiques, enjeux, contrôle social, 1993)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; discipline; histoire des femmes*; histoire et politique; justice reproductive; militance; périodes historiques; québec; régions géographiques; science politique; science politique et droit; thématiques

Femmes en mouvement, trajectoires de l'association féminine d'éducation et d'action sociale 1966-1991 - Lamoureux, Jocelyne; Gélinas, Michèle; Tari, Katy (Boréal, 1993)
Après un chapitre important sur les associations qui ont précédé la fondation de l'AFEAS, l'ouvrage se présente comme un essai d'interprétation critique, avec des éléments d'ordre socio-historique, des activités et de l'influence de l'organisme.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; SAC; amériques; histoire et politique; militance; périodes historiques; québec; régions géographiques; thématiques

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les bâtisseuses de la Cité : actes du Colloque Les Bâtisseuses de la Cité dans le cadre de la Section d'études féministes du Congrès de l'Acfas 1992, 1993)
Keywords: 1600-1699; 1700-1799; 1900-1999; DIG; amérique du nord; amériques; arts; canada; discipline; femmes* artistes; histoire et politique; musique; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Femmes, art et pouvoir et autres essais - Nochlin, Linda (Rayon art, 1993)
Plusieurs essais, rédigés à partir de 1969, qui abordent les sujets des représentations féminines dans l'art, entre la fin du XVIIIe siècle et le XXe siècle, l'érotisme et les images du féminin dans l'art du XIXe siècle et la question pourquoi n'y a-t-il pas eu de grands artistes femmes. L'auteur identifie l'idéologie dominante sur laquelle repose la place donnée aux femmes.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; domination masculine; fem1000; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; rapports de domination; rapports sociaux de sexe; systèmes d'oppressions; thématiques; théories féministes

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

Mais qu’est-ce qu’elles disent ? - Picq, Françoise (Libération des femmes: les années-mouvement, 1993)
Le 26 août 1970 à l'Arc de Triomphe, neuf femmes donnaient par une action symbolique le coup d'envoi d'un mouvement qui allait en une quinzaine d'années bouleverser profondément la société française.A partir de son expérience personnelle, de l'étude des écrits et des archives du Mouvement de libération des femmes, d'une enquête auprès des féministes de la première heure, Françoise Picq présente ici une histoire en trois temps : celui de la découverte, celui des contradictions, puis le temps de la réflexion et du bilan avec les années quatre-vingt.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; inégalités; militance; mouvements de femmes*; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques

Avortement : pratiques, enjeux, contrôle social - Sève, Micheline de; Lamoureux, Diane (Collection Les Entêtées, 1993)
La question de l'avortement, réexaminée par des chercheures féministes. La première partie s'attaque aux pratiques contraceptives des femmes de la Nouvelle-France; on y aborde également un sujet tabou : l'avortement répété. Dans la deuxième partie de l'ouvrage, les auteures analysent la situation qui prévaut dans les pays de l'ex-bloc soviétique et montrent comment l'avortement peut servir d'arme politique contre les femmes. Enfin, la troisième partie porte sur l'idéologie autant des mouvements "pro-vie" que de ceux qui militent en faveur du droit à l'avortement.
Keywords: amérique du nord; amériques; avortement; canada; droits des femmes*; europe; histoire et politique; justice reproductive; militance; pologne; pro-vie; québec; régions géographiques; socialisme; thématiques

Formation de l'État et politiques sociales aux Etats-Unis - Skocpol, Theda (Actes de la recherche en sciences sociales, 1993)
Les Américains éprouvent une certaine méfiance à l'égard de la puissance de l'Etat. Cependant, si l'on analyse l'histoire du développement du pays, on constate que les Etats-Unis ont toujours eu "un Etat". Les changements qui ont affecté l'Etat américain -passé d'un Etat fédéral, non bureaucratique, "Etat de tribunaux et de partis" au XIXe siècle, à un Etat fédéral, partiellement partiellement bureaucratisé, orienté vers l'action en faveur de groupes d'intérêts particuliers au XXe siècle -permettent de comprendre les différentes phases et les modalités de la politique sociale américaine. Les Etats-Unis n'ont pas développé un Etat-providence qui, comme en Europe, assure la protection sociale des ouvriers et de tous les citoyens. Entre 1870 et 1920, la politique sociale des Etats-Unis s'est développée principalement en faveur des anciens combattants et des mères de famille ; après 1930, elle a porté surtout sur la mise en place d'un système d'assurance vieillesse pour les retraités. Les institutions politiques américaines ont favorisé le développement de dépenses sociales importantes pour des groupes sociaux qui ne sont pas les plus démunis.
Keywords: 1800-1899; 1900-1999; amériques; cours; discipline; his4443; histoire et politique; maternité; politique américaine; politiques publiques; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; thématiques; états-unis

Sexual practice/textual theory: Lesbian cultural criticism - Wolfe, Susan J.; Penelope, Julia (B. Blackwell, 1993)
Nous vivons à l'ère postmoderniste, poststructuraliste (et, diraient certain.e.s, postféministe), à ​​une époque où le terme lesbienne pose problème, même lorsqu'il est utilisé de manière non péjorative par une lesbienne autoproclamée. Nous ne pouvons plus parler en tant qu'« individus », semble-t-il ; le faire est d’une naïveté et/ou d’une simplicité impardonnable. Nous ne pouvons parler qu'en tant que « sujets » romancés, nos identités individuelles n'existant que comme la création de textes (de quelqu'un) ou comme le résultat d'une signification. En cent ans, les sexologues allemand.e.s ont « apparu » les lesbiennes pour nous pathologiser et les poststructuralistes français.e.s nous ont « fait disparaître » pour déconstruire les catégories de sexe et de genre et « interroger » « le » sujet. Certains universitaires suggèrent que le féminisme et le postmodernisme ont de nombreux points communs. Les théoricien.nes du postmodernisme des deux côtés de l’Atlantique affirment de la même manière que leur mouvement partage un agenda politique avec le féminisme, dans la mesure où déstabiliser les relations narratives entre dominant.e et subordonné.e, contenant et contenu, c’est aussi déstabiliser les relations sociales et culturelles de domination et de confinement en dans lequel le masculin conventionnel subsume et enveloppe le féminin conventionnel. Dans le jargon actuel, le postmodemisme et le féminisme ont « problématisé les relations de genre », remettant en question le « caractère naturel » des relations de genre et considérant la relation entre les sexes comme le résultat de forces sociales, de langage et/ou de pouvoir (Giroux, 28). ). Ni « l'homme » ni la « femme » ne sont un objet ontologiquement stable, une catégorie invariable ; les deux sont construits dans l’histoire (Fuss, 3). Nous ne contesterons pas l’idée que le terme Lesbienne, pendant la brève période où il a été utilisé, a souvent été un terme d’opprobre et non d’approbation – qu’il a été utilisé linguistiquement pour signifier la déviance et même la monstruosité. Nous ne souhaitons pas non plus tomber dans le genre d’essentialisme qui supposerait que toutes les lesbiennes sont « simplement » des lesbiennes. Nous sommes membres de différentes races, classes, groupes ethniques ; collectivement, les lesbiennes souffrent de nombreuses formes d’oppression. En revanche, la philosophie postmoderne, du moins dans les formes qu'elle a prises au sein des instances du pouvoir (pédagogie académique, théorie esthétique et critique) nous semble menacer d'effacer le réel (ou, comme diraient les postmodernistes, « » matériel ») Lesbiennes. Si l’identité est construite par des textes, peut-être n’existe-t-il pas de personne (« objet ») comme lesbienne, aucune caractéristique (non construite) que partagent les lesbiennes. Si les textes et l'identité individuelle peuvent être déconstruits, peut-être que n'importe qui, même non-lesbienne, pourra « lire comme une lesbienne », comme certains l'ont suggéré. Mais s’il n’y a pas d’identité lesbienne en tant que telle, alors l’affirmation selon laquelle on « lit en tant que lesbienne » est un non-sens. Le discours postmoderniste cherche à déplacer les notions humanistes libérales du soi, du « sujet bourgeois » (H. Foster, 77, cité dans Waugh, 8). Mais comme le note Waugh (8-9), le moi unifié postulé par l’humanisme libéral n’était/n’est pas un moi féminin, et encore moins un moi lesbien. La subjectivité, historiquement construite et exprimée à travers l'équation phénoménologique soi/autre, repose nécessairement sur l'« altérité » féminine de l'« individuité » masculine. Le centre subjectif des discours socialement dominants (du « je » philosophique et rationnel de Descartes au phallique/symbolique psychanalytique de Lacan) en termes de pouvoir, d'action et d'autonomie a été un sujet « universel » qui a établi son identité à travers la marginalisation ou l'exclusion invisible de ce qu'elle a également défini comme la « féminité » (qu'il s'agisse du non-rationnel, du corps, des émotions ou du pré-symbolique). Le « féminin » devient ainsi ce qui ne peut s'exprimer parce qu'il existe en dehors du domaine de la signification symbolique. Constitué à travers un regard masculin et donc doté du mystère de celui dont le statut objectif est perçu comme absolu et définitif. Un . . . devient une femme... Dans la relation dialectique entre l'humanisme traditionnel et l'antihumanisme postmoderne apparu dans les années 1960, les femmes continuent d'être déplacées. Comment peuvent-ils aspirer, rejeter ou synthétiser un nouveau mode d’être à partir d’une thèse qui n’a jamais contenu ou exprimé ce qu’ils ont ressenti comme étant leur expérience historique ?
Keywords: amériques; anthologie; approches et analyses; arts; discipline; histoire et politique; lesbianisme; outils; ouvrages de références; personnes lesbiennes; postmodernisme; régions géographiques; sexualité; thématiques; états-unis; études littéraires

Nothing mat(t)ers: A feminist critique of postmodernism - Brodribb, Somer (J. Lorimer, 1992)
Nothing Mat(t)ers est une critique féministe des théories de Foucault, Derrida et Lacan, entre autres. Somer Brodribb analyse les textes et les arguments que le poststructuralisme a désignés comme centraux, exposant ainsi la misogynie en leur cœur. Brodribb fournit une histoire des définitions du structuralisme, du poststructuralisme, de la déconstruction et du postmodernisme
Keywords: approches et analyses; cours; discours dominant; fem1000; genre; histoire et politique; identités LGBTQIA2+; inégalités; patriarcat; postmodernisme; premier cycle; ressource en ligne; systèmes d'oppressions; thématiques

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

L'Histoire des femmes au Québec depuis quatre siècles - Collectif Clio. (Le Jour, 1992)
Dans une version revue et mise à jour de l'édition de 1982 (Quinze), cet ouvrage repère, du début du xviie siècle à nos jours, les changements qui ont affecté les Québécoises ainsi que les phénomènes qui ont marqué un point tournant dans la transformation de leur image et de leur rôle au sein de notre société. Des figures anonymes – paysannes, autochtones, immigrantes, etc. – à celles qui ont occupé le devant de la scène, toutes les femmes qui ont redéfini le paysage féminin y ont droit de cité.
Keywords: 1600-1699; amériques; cours; cycles supérieurs; fem1000; fem7000; his4550; histoire des femmes*; histoire et politique; lit3220; lit3495; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Le Sexe des sciences : les femmes en plus - Collin, Françoise (Autrement, 1992)
Les femmes n'aiment pas les sciences. Les sciences n'aiment pas les femmes." Cette opinion repose sur un postulat : les femmes seraient tout entières du côté de l'intuition et de la sensibilité, les sciences du côté d'une pure rationalité. Et si ces "évidences" séculaires, confirmées par la longue exclusion des femmes des pratiques scientifiques, n'étaient qu'une histoire d'interdits, d'obstacles, de préjugés et de pouvoir? En effet, l'entrée des femmes dans l'enceinte sacrée des sciences et des technologies et une meilleure connaissance tant des femmes que du travail scientifique remettent aujourd'hui en cause leur prétendue incompatibilité. Réponses à quelques questions, entre autres : quelles sont les conditions d'accès à l'activité et à la création scientifiques, et par quelles procédures les femmes s'en trouvent-elles encore si souvent écartées? Comment cependant les femmes ont-elles contribué et contribuent-elles au développement des sciences? Leur entrée dans ce domaine peut-elle produire des effets sur le fonctionnement du savoir, sur l'éthique ou la politique de la recherche? Bref, la science a-t-elle un sexe?
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; femmes*; histoire et politique; premier cycle; sciences; sexisme; stéréotypes; systèmes d'oppressions; thématiques

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (NRF essais, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Indigena: perspectives autochtones contemporaines - McMaster, Gerald R.; Martin, Lee-Ann; Bérubé, Christian; Canadian Museum of Civilization (Musée canadien des civilisations, 1992)
Publié à l'occasion du 500e anniversaire de la découverte de l'Amérique, ce catalogue regroupe des essais et des textes d'artistes et une documentation des travaux de 19 artistes afin de dénoncer le caractère eurocentrique des célébrations. Alors que Webster et Ippellie revoient les effets de la colonisation sur le patrimoine amérindien et sur celui des peuples de l'Arctique, Wendayete examine la logique matérialiste de l'historiographie canadienne non-autochtone et l'oppose à un concept d'américité philosophique. Todd et Young Man s'attaquent respectivement aux notions de postmodernisme et de ghettoïsation en art. Comprend des textes d'artistes.
Keywords: amériques; approches et analyses; canada; cours; féminisme autochtone; har4610; histoire et politique; premier cycle; régions géographiques; thématiques

Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

The persistent desire: A femme-butch reader - Nestle, Joan (Alyson publ, 1992)
Dans cette anthologie « canonique » des identités Butch-Femme, Joan Nestle retrace 200 ans d'histoire lesbienne, des lettres aux mémoires en passant par les nouvelles. Nestlé passe en revue une décennie de tentatives visant à reconstruire et à comprendre le sens et la valeur des relations butch-femme pour la lesbienne contemporaine, en s'appuyant sur l'histoire orale, la fiction, la poésie et le fantastique.
Keywords: amériques; anthologie; arts; butch/femme; discipline; désir; histoire et politique; littérature; personnes lesbiennes; poésie; ressource en ligne; régions géographiques; sexualité; thématiques; états-unis; études littéraires

Imagined communities: Reflections on the origin and spread of nationalism - Anderson, Benedict (Verso, 1991)
L'ouvrage mondialement connu sur les origines et le développement du nationalisme Toute l'ampleur de la réussite intellectuelle de Benedict Anderson est toujours appréciée et débattue. "Imagined Communities" reste le livre le plus influent sur les origines du nationalisme, comblant le vide qui existait auparavant dans les traditions de la pensée occidentale. Cité plus souvent que tout autre ouvrage de langue anglaise en sciences humaines, il est lu dans le monde entier dans plus de trente traductions. Rédigée avec une clarté exemplaire, cette étude éclairante retrace l'émergence de l'idée de communauté en Amérique du Sud, plutôt qu'en Europe au XIXe siècle. Plus tard, ce sentiment d'appartenance s'est formé et reformulé à tous les niveaux, de la haute politique à la culture populaire, en passant par l'imprimé, la littérature, les cartes et les musées. Suite à la montée et au conflit des nations et au déclin des empires, Anderson s'appuie sur des exemples de l'Asie du Sud-Est, de l'Amérique latine et du passé récent de l'Europe pour montrer comment le nationalisme a façonné le monde moderne.
Keywords: approches et analyses; colonialisme; communication; cours; discipline; discours dominant; fem1000; histoire; histoire et politique; identités culturelles; modernité; mémoire collective; mémoire culturelle; nationalisme; occident; politique; premier cycle; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty--and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Mais à quoi sert une épistémologie des rapports sociaux de sexe? - Combes, Danièle (Sexe et genre. De la hierarchie entre les sexes, 1991)
S’inscrivant dans le mouvement des études féministes qui ont marqué les années quatre-vingt, cet ouvrage réunit les différents points de vue de femmes universitaires engagées dans des champs de recherches aussi divers que la biologie, le droit, la linguistique. Partant de l’examen critique de la distinction sexe et genre, elles analysent les mécanismes qui assurent le maintien de la domination masculine et font progresser la réflexion sur les déterminants de la subordination des femmes.
Keywords: 1900-1999; 1980-1989; approches et analyses; classe sociale; cours; discipline; europe; fem1000; france; histoire et politique; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; épistémologie

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Histoire des femmes en Occident - Duby, Georges; Perrot, Michelle (Plon, 1991)
Projet démesuré que de couvrir près de vingt siècles d'histoire du monde antique gréco-romain, de parcourir un espace qui va des rivages de la Méditerranée à ceux des mers du Nord, des colonnes d'Héraklès aux rives de l'Indus, de se plonger dans des documents aussi divers que les tombes d'une nécropole, la stèle inscrite plaquée aux murs du sanctuaire, le rouleau de papyrus, la scène peinte sur la panse d'un vase... et une littérature grecque et latine qui, si elle n'a pas donné la parole aux femmes, a beaucoup parlé d'elles. On l'aura deviné, ce livre n'a pas pour fonction de remplacer l'énorme production qui existe en ce domaine. Il aborde un petit nombre seulement des questions qui nous ont paru importantes pour aider à comprendre la place des femmes dans le monde antique et, plus encore peut-être, dans la perspective d'un ensemble de volumes traitant de l'histoire des femmes, comprendre les fondements d'habitudes mentales, de mesures juridiques, d'institutions sociales qui ont duré des siècles en Occident.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; antiquité; approches et analyses; conditions des femmes*; cours; discipline; europe; his4330; histoire; histoire des femmes*; histoire et politique; incontournable; lit3220; moyen-âge; occident; oui; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Le temps de la division 1845-1865 - Evans, Sara Margaret (Les américaines : histoire des femmes aux Etats-Unis, 1991)
Keywords: 1800-1899; amériques; conflit; cours; fem1000; histoire des femmes*; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis

Les américaines : histoire des femmes aux Etats-Unis - Evans, Sara Margaret (Belin, 1991)
Ce livre souhaite replacer les témoignages, les vécus et les expériences des femmes américaines dans l'histoire plus vaste de la nation. L'analyse qu'elle dresse ne se limite pas aux seules femmes blanches américaines mais embrasse également la situation des femmes des premières nations et des femmes afroaméricaines, esclaves, femmes libres, ouvrières ou femme au foyer. C'est par soucis de préserver la diversité des situations, des faits et des modes de vie, que Sara M. Evans opère une classification selon des critères géographiques et de classe : elle distingue les femmes qui appartiennent à un milieu urbain de celles qui vivent en milieu rural, en évoquant les caractéristiques qui leurs sont propres selon des critères sociaux-professionnels. Il s'agit de comprendre comment les femmes américaines ont redéfini constamment leur place dans la société et fait évoluer les sphères privées et publiques tout comme les législations et les rapports sociaux, cela depuis les premières femmes amérindiennes arrivées sur le continent il y a 2000 ans, jusqu'aux les femmes modernes de nos temps.
Keywords: 1800-1899; amériques; classe sociale; conflit; cours; fem1000; femmes* afro-américaines; femmes* autochtones; histoire des femmes*; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; témoignage; états-unis

Odd girls and twilight lovers: A history of lesbian life in twentieth-century America - Faderman, Lillian (Between men-between women, 1991)
Comme l'écrit Lillian Faderman, il n'y a « pas de constante en matière de lesbiennes », si ce n'est que les lesbiennes préfèrent les femmes. Dans ce livre révolutionnaire, elle récupère l’histoire de la vie lesbienne dans l’Amérique du XXe siècle, retraçant l’évolution de l’identité et des sous-cultures lesbiennes depuis les premiers réseaux jusqu’aux modes de vie divers plus récents. Elle puise dans des journaux, des manuscrits inédits, des chansons, des comptes rendus médiatiques, des romans, de la littérature médicale, des artefacts de la culture pop et des histoires orales de lesbiennes de tous âges et de tous horizons, découvrant un récit d'une profondeur et d'une originalité hors du commun.
Keywords: 1900-1999; amériques; approches et analyses; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; régions géographiques; thématiques; états-unis

La république des hommes: les Patriotes de 1837 face aux femmes - Greer, Allan (Revue d'histoire de l'Amérique française, 1991)
Cet article examine la dimension sexuelle de la Rébellion de 1837 dans le Bas-Canada et soutient que les femmes furent bien moins actives dans la lutte anti-gouvernementale qu'elles ne l'avaient été au XVIIIe siècle dans diverses émeutes et autres mouvements de résistance. L'explication de ce changement est liée au procès de « masculinisation » de la politique qui a lieu un peu partout en Occident à la même époque. Comme le républicain type de la première moitié du XIXe siècle, le patriote du Bas-Canada défend une conception essentiellement masculine de la citoyenneté en régime démocratique. D'autre part la conviction rousseauiste que la femme vertueuse doit se confiner dans son rôle domestique permet de comprendre les poussées occasionnelles de mysoginie contre les femmes qui affichent publiquement leur opposition au mouvement patriote.
Keywords: 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; his4550; histoire; histoire et politique; politique; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Feminist Debates about Women and National Socialism - Grossmann, Atina (Gender & History, 1991)
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; cours; discipline; europe; fascisme; his4830; histoire; histoire des femmes*; histoire et politique; historiographie; holocauste; maternité; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; thématiques; violences; violences contre les femmes*; violences d'état; violences sexuelles

Idola Saint-Jean et le radicalisme féministe de l’entre-deux-guerres - Lamoureux, Diane (Recherches féministes, 1991)
Les suffragistes nous semblent souvent de bonnes bourgeoises aux méthodes et aux idées surannées. Pourtant, le féminisme de l'entre-deux-guerres est aussi diversifié que le féminisme actuel. Il est utile d'analyser ce passé féministe dans le contexte du mouvement de réforme sociale de l'époque pour ensuite apprécier le radicalisme de la pensée politique d'Idola Saint-Jean, une pensée politique marquée au coin de la justice sociale, de la démocratie et d'un sens aigu de l'antagonisme entre les sexes qui conditionne son activité militante
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; discipline; droit de vote; droits des femmes*; histoire et politique; justice sociale; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; suffragettes; thématiques

De la mère patriarcale à la mère légendaire : Triptyque lesbien de Jovette Marchessault - Saint-Martin, Lori (Voix et Images, 1991)
Keywords: amériques; approches et analyses; arts; discipline; histoire et politique; maternité; patriarcat; personnes lesbiennes; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

La main tranchante du symbole : textes et essais féministes - Bersianik, Louky (Les éditions du remue-ménage, 1990)
Une anthologie au sous-titre explicite qui regroupe des textes écrits essentiellement entre 1980 et 1990, "choisis à cause de leur perspective féministe et" de "leur vision particulière de la symbolique patriarcale" (selon l'auteure, la société patriarcale est "meurtrière, hypocrite et mensongère"). Le regroupement des textes a été réalisé selon divers thèmes couvergents : l'écriture, la langue, la critique (p. 199-221), les nouvelles techniques de reproduction, la mémoire du futur, etc. Quelques textes inédits. Extraits de ##L'Euguélionne##, p. 66-91.
Keywords: amériques; antiféminisme; approches et analyses; cours; discipline; fem1000; histoire et politique; militance; mémoire collective; pratiques féministes; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Women, art, and society - Chadwick, Whitney (Thames and Hudson, 1990)
L'étude à succès acclamée de l'historienne de l'art Whitney Chadwick remet en question l'hypothèse selon laquelle les grandes femmes artistes sont des exceptions à la règle qui ont « transcendé » leur genre pour produire des œuvres d'art majeures. Tout en présentant certaines des nombreuses femmes depuis le Moyen Âge dont les contributions à la culture visuelle ont souvent été négligées, l'enquête de Chadwick réexamine les œuvres elles-mêmes et la manière dont elles ont été perçues comme marginales, souvent en référence directe au genre. Dans sa discussion sur le féminisme et son influence sur une telle réévaluation, elle aborde également les questions étroitement liées de l'ethnicité, de la classe et de la sexualité.
Keywords: LGBTQIA2+; amériques; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; régions géographiques; sexualité; thématiques; états-unis

L'épopée du suffrage féminin au Québec (1920-1940) - Darsigny, Maryse (Service aux collectivités de l'UQAM, 1990)
Perte et reconquête du droit de vote des femmes. La structuration du mouvement pour le suffrage féminin au Québec. Les réactions contre le suffrage féminin. Les suffragettes persistent. L'année historique pour les Québécoises.
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; SAC; amériques; droit de vote; droits des femmes*; histoire et politique; périodes historiques; québec; régions géographiques; suffragettes; thématiques

Instabili: la question du sujet = the question of subject - Fraser, Marie; Johnstone, Lesley; Baril, Céline (Artextes, 1990)
Instabili: La question du sujet, sous la direction de Marie Fraser et Lesley Johnstone Publiés à l’occasion du 16e anniversaire de Powerhouse, sept textes et cinq projets d’artistes questionnent les multiples rapports existant entre féminisme et arts visuels, et proposent également une histoire de la galerie. L’ouvrage inclut aussi une chronologie des événements (1973-1989) qui ont marqué cette histoire. Textes de Marie Fraser, Christine Ross, Mary Kelly, Catherine Bédard, Liz Magro, Joanna Nash, Thérèse St-Gelais et Nell Tenhaaf.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; artistes féministes; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Carol - Highsmith, Patricia (Calmann-Lévy, 1990)
Elles se regardèrent au même instant. Thérèse avait levé les yeux de la boîte qu’elle était en train d’ouvrir et la femme venait de tourner la tête vers elle. Elle était grande et blonde, longue silhouette gracieuse dans un ample manteau de fourrure, qu’elle tenait entrouvert, la main posée sur la hanche. Ses yeux étaient gris, décolorés et pourtant lumineux comme le feu, et ceux de Thérèse, captifs, ne purent s’en détacher. Elle entendit la cliente qui lui faisait face répéter une question et elle resta muette. La femme la regardait, elle aussi, l’air préoccupé comme si une partie de son attention était fixée sur l’achat qu’elle s’apprêtait à faire et, bien qu’il y eût plusieurs vendeuses entre elles deux, Thérèse fut certaine qu’elle allait venir vers elle. Carol est le récit d’une obsession. Refusé à l’origine par son éditeur américain, ce roman a paru une première fois en France sous le titre Les Eaux dérobées signé du pseudonyme de Claire Morgan. Sa réédition permet de redécouvrir l’un des ouvrages les plus marquants du XXe siècle, injustement méconnu. Si le sujet ne fait aujourd’hui plus scandale, Carol conserve son odeur sulfureuse et figure parmi les oeuvres cultes de la littérature lesbienne. Patricia Highsmith y dévoile avec force et sensibilité un amour qui revendique sa liberté dans l’Amérique des années 50.
Keywords: 1900-1999; 1950-1959; amour; amériques; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; roman; régions géographiques; sexualité; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

De travail et d'espoir. Des groupes se racontent le féminisme - Landry, Simone; Kurtzman, Lyne (Les éditions du remue-ménage, 1990)
Bilan de l'évolution de la condition des femmes au Québec. Les trois premiers chapitres traitent des groupes locaux et régionaux, des associations provinciales et des groupes syndicaux; on y décrit ce que sont ces groupes féministes et quels sont les thèmes sur lesquels portent leur réflexion et leur action. Le dernier chapitre est un bilan de l'ensemble de la réflexion et l'action des groupes de femmes féministes au Québec.
Keywords: SAC; amériques; approches et analyses; droits des femmes*; groupes de femmes; histoire des femmes*; histoire et politique; justice sociale; militance; québec; régions géographiques; thématiques

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques

Les Québécoises et la conquête du pouvoir politique : enquête sur l'émergence d'une élite politique féminine au Québec - Maillé, Chantal (Éditions Saint-Martin, 1990., 1990)
Keywords: amériques; cours; fem1000; femmes* politiques; histoire et politique; premier cycle; québec; ressource en ligne; régions géographiques; thématiques

L'amour sous Victoria : sexualité et classes populaires à Londres au XIXe siècle - Barret-Ducrocq, Françoise (Plon, 1989)
Keywords: 1800-1899; amour; approches et analyses; classe ouvrière; cours; discipline; discours dominant; europe; his4860; histoire; histoire de la sexualité; histoire et politique; inégalités; londres; premier cycle; périodes historiques; rapports sociaux de sexe; royaume-uni; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; époque victorienne

Stratégies du vertige. Trois poètes :Nicole Brossard, Madeleine Gagnon, France Théoret - Dupré, Louise (Itinéraires féministes, 1989)
Nicole Brossard, Madeleine Gagnon et France Théoret ont eu sans contredit une influence déterminante sur notre littérature. Plus qu’une étude de ces trois poètes, Stratégies du vertige nous propose de suivre un trajet amorcé dans les années 1970, au coeur des débats sur la modernité et sur l’écriture des femmes.
Keywords: amériques; arts; discipline; histoire et politique; poésie; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Le rapt de Ganymède - Fernandez, Dominique (Bernard Grasset, 1989)
"D'après la mythologie grecque, Ganymède était le plus bel adolescent vivant sur la terre. Zeus, le dieu suprême, étant tombé amoureux du jeune homme, prit la forme d'un aigle pour l'enlever et en faire son compagnon dans le ciel. Le rapt de Ganymède est resté le symbole de l'audace nécessaire à un amour qui défie les règles communes. Quand j'étais étudiant, deux mots étaient synonymes : homosexuel et paria. Aux hommes et aux femmes de ma génération a manqué la possibilité de découvrir, chez des modèles que le monde entier admire, une légitimation de goûts que l'opinion publique réprouve sous l'épithète de "contre nature". J'ai voulu montrer, d'une part que la persécution de l'homosexualité à partir du XIXe siècle s'explique par des raisons exclusivement économiques et politiques, d'autre part que certains des plus grands esprits, des meilleurs poètes et romanciers, compositeurs de musique, peintres et cinéastes de tous les temps, de Sapho à Platon, de Whitman à Cavafy, de Melville à Yourcenar, du Caravage à David, de Mozart à Schubert, d'Eisenstein à Visconti, ont tissé un réseau d'oeuvres qui peuvent servir désormais de culture, c'est-à-dire d'exemple et d'encouragement. Bien mieux que les paternes et hypocrites absolutions prononcées depuis cent ans par les psychiatres et psychanalystes, véritable imposture de notre temps, dévoilée ici dans un sottisier réjouissant. D.F." -- Site de l'éditeur
Keywords: 1800-1899; 1900-1999; DIG; LGBTQIA2+; approches et analyses; arts; beaux-arts; cinéma; cours; discipline; europe; his4860; histoire; histoire de l'art; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; littérature homosexuelle; musique; mythologie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques

Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture,, 1989)
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Identité sexuelle/sexuée/de sexe? Trois modes de conceptualisation du rapport entre sexe et genre - Mathieu, Nicole-Claude (Catégorisation de sexe et constructions scientifiques, 1989)
Keywords: approches et analyses; corps; cours; discipline; discours dominant; essentialisation; féminisme matérialiste; genre; histoire et politique; identité sexuelle; identités; naturalisation; philosophie politique; premier cycle; sciences; sciences humaines; sex3383; sexe; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; épistémologies féministes

Surname Viet given name Nam - Trinh, T. Minh-Ha (Thi Minh-Ha) (Women Make Movies, 1989)
Un essai sur la répression des femmes dans la société vietnamienne. Le film est centré sur la culture vietnamienne vue au travers de l'histoire de résistance des femmes, la tradition orale, les images encouragées par les medias ainsi que la vie et les regards des femmes vietnamiennes.
Keywords: approches et analyses; asie; cours; fem3200; histoire et politique; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; vietnam

Polity and Group Difference: A Critique of the Ideal of Universal Citizenship - Young, Iris Marion (Ethics, 1989)
Keywords: approches et analyses; cours; discipline; droits civiques; histoire et politique; intersectionnalité; justice sociale; philosophie politique; pol4212; premier cycle; science politique; science politique et droit; sciences humaines; thématiques

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

chapitre 3, « Les couvents comme expression organisée des aspirations des femmes » dans Profession: religieuse : un choix pour les Québécoises, 1840-1920 - Danylewycz, Marta; Linteau, Paul-André; Prentice, Alison; Westfall, William (Profession: religieuse : un choix pour les Québécoises, 1840-1920, 1988)
Marta Danylewycz s'intéresse à 2 communautés: les soeurs de Notre-Dame et de la Miséricorde, qui rassemblent près du cinquième de la population religieuse féminine au tournant du siècle.
Keywords: 1800-1899; 1840-1849; 1850-1859; 1860-1869; 1870-1879; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

Can the Subaltern Speak? - Spivak, Gayatri Chakravorty (Marxism and the Interpretation of Culture, 1988)
Keywords: 1900-1999; 1980-1989; approches et analyses; cours; fem1000; histoire et politique; incontournable; inégalités; mondialisation; pol4022; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; théories féministes; études postcoloniales

In other worlds essays in cultural politics - Spivak, Gayatri Chakravorty (Routledge, 1988)
Dans cet ouvrage classique, Gayatri Chakravorty Spivak, l'une des théoriciennes de la culture les plus importantes et les plus influentes travaillant aujourd'hui, analyse la relation entre la langue, les femmes et la culture dans des contextes occidentaux et non occidentaux. Développant une intégration originale de puissantes méthodologies contemporaines - déconstruction, marxisme et féminisme - Spivak tourne ce nouveau modèle sur les grands débats de l'étude de la littérature et de la culture, assurant ainsi que In Other Worlds est devenu un outil précieux pour étudier notre propre monde et celui des autres cultures.
Keywords: 1900-1999; 1980-1989; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; histoire et politique; international; lit3220; premier cycle; périodes historiques; thématiques; théories féministes; théories littéraires; études littéraires; études postcoloniales

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Exotisme et altérité: Essai sur les fondements d'une critique de l'anthropologie - Affergan, Francis (Sociologie d'aujourd'hui, 1987)
Keywords: anthropologie; approches et analyses; cours; discipline; har4610; histoire et politique; premier cycle; racisme; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Le triangle rose : la déportation des homosexuels (1933-1945) - Boisson, Jean (Laffont, 1987)
Keywords: 1900-1999; LGBTQIA2+; allemagne; approches et analyses; camps de concentration; cours; discipline; discours dominant; europe; his4860; histoire; histoire de la sexualité; histoire et politique; holocauste; homophobie; homosexualité; hétérosexisme; identités LGBTQIA2+; nazisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; seconde guerre mondiale; sexualité; systèmes d'oppressions; thématiques

L’approche féministe en termes de rapports sociaux ou l’art de survivre sur la corde raide en talons hauts! - Bourgon, Michèle (Service social, 1987)
Préoccupée d'une part par la situation des femmes qui, suite aux bouleversements provoqués par les luttes féministes, ont à vivre sous la pression de messages sociaux contradictoires, intéressée d'autre part par les pratiques sociales qui, dans le contexte actuel de transformations basées sur la rationalisation des budgets et des services, se trouvent confrontées à des visions divergentes quant à la nature et la fonction de l'intervention sociale, Pauteure expose et illustre une approche d'intervention féministe visant la défense des intérêts des femmes et la transformation des rapports sociaux dominants.
Keywords: approches et analyses; cours; discipline; discours dominant; histoire et politique; justice sociale; premier cycle; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

Des cailloux blancs pour les forêts obscures - Marchessault, Jovette (Collection Roman québécois, 1987)
Qualifié à sa parution en 1987 de « roman du troisième œil » par Gloria F. Orenstein, ce livre raconte un moment dans la vie de Jeanne – depuis sa retraite des Appalaches, au sein d’une petite communauté d’esprits nouveaux –, alors que se meurt sa compagne, Noria. Aviatrice, cette dernière sauve des laboratoires les bêtes torturées à des fins de recherches expérimentales. Sur le seuil de sa vie revient son père, le Lion de Bangor, avec qui elle s’était réconciliée. Ce médecin, qui étudie les cellules souches du cancer, lève enfin pour Jeanne l’écrivaine les derniers voiles sur la vie de Noria : sa naissance, son enfance au sein du Ku Klux Klan, ce fils qu’elle a perdu, et cet amour infini que le Lion lui porte, un amour « comme ces ponts miraculeux sur lesquels nous avançons les uns vers les autres. » « Ce dernier volet de la trilogie Comme une enfant de la terre met en scène Noria, une aviatrice qui, telle une chamane, vole à travers le ciel nocturne de l’Amérique du Nord pour livrer au monde un message de salut et un espoir de guérison, et Jeanne, l’écrivaine qui pratique son propre art magique de la guérison : l’art de la littérature. » — GLORIA F. ORENSTEIN
Keywords: 1900-1999; amériques; approches et analyses; care; histoire et politique; hétérosexisme; littérature québécoise; périodes historiques; racisme; roman; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Popular culture critical readers, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. --back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Les femmes dans le mouvement surréaliste - Chadwick, Whitney (Chêne, 1986)
Le surréalisme est sans conteste le mouvement artistique du XXe siècle qui a le plus célébré la femme. Celle-ci fut même la source d'inspiration de la plupart des œuvres produites dans le mouvement : muse, femme-enfant, sorcière ou encore maîtresse, elle a dominé la poésie et la peinture surréalistes. Mais cette célébration, qui fait de la femme une inspiratrice de la vie créatrice de l'homme, cache le rôle très actif que les femmes artistes ont joué au sein du mouvement. Peintres, écrivains, photographes, elles ont eu une production riche et originale et ont participé à toutes les manifestations et toutes les expositions internationales déterminantes. Cet ouvrage, fruit de dix années de recherches à Londres, Paris, New York et Mexico, nous fait découvrir sous un nouveau jour les biographies et les œuvres de ces femmes remarquables qui ont dû, pour acquérir leur identité artistique, s'opposer aux préjugés de leur temps : Leonora Carrington, Dora Maar, Frida Kahlo, Lee Miller, Léonor Fini, Toyen, Dorothea Tanning... Jeunes et audacieuses, elles contribuèrent à créer l'imagerie visuelle de leur époque et furent, en ce sens, les messagères du futur. Whitney Chadwick a rassemblé dans ce livre interviews, correspondances, poèmes et témoignages ainsi que plus de deux cents photographies, dessins et peintures afin de nous donner pour la première fois une véritable histoire du rôle de la femme dans le mouvement surréaliste pendant les années tumultueuses de l'avant-guerre et de la guerre.
Keywords: 1900-1999; 1930-1939; 1940-1949; amériques; approches et analyses; art moderne; cours; discours dominant; europe; femmes* artistes; france; har4600; histoire et politique; londres; mexico; mexique; new york; paris; patriarcat; premier cycle; périodes historiques; royaume-uni; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

Le livre de la cité des dames - De Pisan, Christine (Série "Moyen Age", 1986)
Traduction, Introduction par Éric Hicks et Thérèse Moreau À la plus italienne des Parisiennes du XVe siècle revint la gloire de défendre l’honneur des femmes : en 1405, Christine de Pizan achevait le Livre de la Cité des dames qui donnait en exemple les femmes illustres de tous les temps. Il y eut ensuite le Livre des trois vertus ou Trésor de la Cité des dames, où Christine faisait une analyse lucide et précise de la société française, vue du côté féminin, détaillant tous les «états des femmes» et donnant de chacun, depuis celui des princesses jusqu’à celui des femmes de laboureur, une vision réaliste et positive. La première, elle avait compris que les femmes avaient une place à elles dans la société politique. Née à Venise vers 1365, Christine vient, à quatre ans, vivre à Paris où son père, Thomas de Pizan, médecin et astrologue, a été appelé par Charles V. Elle défend les femmes en rassemblant un large éventail de femmes célèbres à travers l'histoire. Ces femmes sont «logées» dans la Cité des Dames, qui est en fait le livre. Alors que Pizan construit sa ville, elle utilise chaque femme célèbre comme un élément constitutif non seulement des murs et des maisons de la ville, mais aussi comme éléments constitutifs de sa thèse. Chaque femme ajoutée à la ville ajoute à l'argument de Pizan selon lequel les femmes sont des participantes valorisées dans la société. Elle plaide également en faveur de l'éducation des femmes.
Keywords: cours; discipline; europe; fem1000; histoire; histoire des femmes*; histoire et politique; incontournable; littérature; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; écriture des femmes*; éducation; études littéraires

Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements -- Leisure and Labor -- Putting on Style -- Dance Madness -- The Coney Island Excursion -- Cheap Theater and the Nickel Dumps -- Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*

Le pourquoi je mentionne les femmes - Tristan, Flora (Union ouvrière : suivie de lettres de Flora Tristan, 1986)
Keywords: 1800-1899; classe sociale; cours; discipline; fem1000; histoire; histoire et politique; incontournable; militance; premier cycle; périodes historiques; sciences humaines; thématiques; théories féministes

Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." --From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Le féminisme égalitaire - Castro, Ginette (Radioscopie du féminisme américain, 1984)
Keywords: 1900-1999; amériques; cours; discipline; fem1000; histoire du féminisme; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; thématiques; états-unis

Radioscopie du feminisme americain - Castro, Ginette (Presses de la Fondation nationale des sciences politiques, 1984)
En explorant tous les aspects du féminisme américain (historique, idéologique, culturel, politique), ce livre montre que la prise de conscience des féministes américaines s'est effectuée, de 1945 à nos jours, de manière continue et progressive. Malgré les dénégations du mouvement féministe, le néoféminisme est issu de la réflexion d'une élite féminine professionnelle ou intellectuelle. L'apport original de l'auteur à la connaissance du féminisme américain est sa certitude, étayée par ses observations, que l'expression la plus accomplie de la culture féministe est la production littéraire. Là réside la garantie de survie d'un mouvement divisé tant dans ses courants idéologiques que dans ses modes d'action. Malgré ses limites, le mouvement de libération des femmes est irréversible et sa formulation est la plus large que le féminisme ait jamais atteint.
Keywords: 1900-1999; amériques; cours; cycles supérieurs; fem1000; fem9000; histoire du féminisme; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Une Histoire des femmes est-elle possible? - Perrot, Michelle (Rivages, 1984)
Les femmes ont-elles une histoire ? Pourquoi cette histoire n’a-t-elle pas été écrite dans le passé et pourquoi se développe-t-elle depuis une dizaine d’années ? De quelles sources dispose-t-on à cet égard et cette démarche implique-t-elle des méthodes particulières ? Que signifient « mémoire », « culture », « pouvoir » des femmes ? La catégorie de sexe est-elle, comme celle des âges, une variable historique issue des nouveaux classements induits par le développement de l’individualisme ? ou quelque chose de plus ? Voilà quelques unes des questions abordées dans ce livre qui prend en compte le changement de direction du regard historique lorsque l’on pose la question du rapport des sexes comme central. Avec la participation d’Alain Corbin, Arlette Farge, Agnès Fine, Catherine Fouquet, Geneviève Fraisse, Christiane Klapisch, Yvonne Knibiehler, Michelle Perrot, Elisabeth Ravoux-Rallo, Jacques Revel, Anne Roche, Pauline Schmitt-Pantel, Sylvie Van de Casteele, Danièle Voldman.
Keywords: arts; cours; discipline; france; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

American women artists, past and present: a selected bibliographic guide - Tufts, Eleanor (Garland reference library of the humanities, 1984)
Keywords: amériques; arts; bibliographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; pol4022; premier cycle; régions géographiques; thématiques; états-unis

Tactiques des suffragettes anglaises : espace des hommes et corps des femmes - Vicinus, Martha (Stratégies des femmes, 1984)
Keywords: approches et analyses; cours; droit de vote; europe; fem1000; histoire et politique; militance; premier cycle; rapports sociaux de sexe; royaume-uni; régions géographiques; suffragettes; thématiques

Chapitre 2. Le mouvement anti-esclavagiste et la naissance des droits des femmes. - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; corps; cours; discipline; droits des femmes*; esclavagisme; féminisme afroaméricain; féminismes noirs; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; états-unis

Resistance to oppression: Black women's response to slavery in the united states - Ellison, Mary (Slavery & Abolition, 1983)
Keywords: afro-féminisme; amériques; approches et analyses; cours; esclavagisme; fem3100; femmes* afro-américaines; féminisme afroaméricain; histoire et politique; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme

Nous sommes le produit d’un contexte - O'Leary, Véronique; St-Pierre, Josée.; Toupin, Louise (Québécoises deboutte! Tome 1. Une Anthologie de textes du Front de libération des femmes (1969-1971) et du Centre des femmes (1972-1975)., 1983)
Le volume 1 (212 p.) comprend des tracts, documents internes, manifestes et lettres diffusées par les deux groupes entre 1969 et 1975, de même qu'un aperçu de la couverture de presse dont ils bénéficièrent à l'époque. Le volume 2 (377 p.) reprend la collection complète du journal ##Québécoises deboutte## publié entre 1972 et 1975, par le Centre des femmes; on y a ajouté des tables rondes.
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; histoire et politique; inégalités; militance; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

La Québécoite: roman - Robin, Régine (Collection Littérature d'Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"--
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; droits civiques; fem1000; fem3300; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires

Art et féminisme - Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec); Arbour, Rose-Marie; Murgia, Pierre; Musée d'art contemporain (Québec) (Ministère des affaires culturelles, 1982)
Catalogue de l'exposition Art et féminisme qui eut lieu en 1982 au Musée d'Art Contemporain de Montréal (MAC).
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Icon editions, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

Nous nous définissons comme esclaves des esclaves - Front de libération des femmes du Québec (Québécoises deboutte!, 1982)
Keywords: 1900-1999; amériques; cours; fem1000; histoire des femmes*; histoire et politique; militance; mouvements sociaux; nationalisme; premier cycle; périodes historiques; québec; régions géographiques; thématiques

Québécoises deboutte! - O'Leary, Véronique; Toupin, Louise (De mémoire de femmes, 1982)
Québécoises Deboutte! c’est non seulement l’accession à l’écriture de ce féminisme québécois organisé sur la base d’un groupe autonome de militantes, mais c’est aussi la première revue d’analyse théorique de l’exploitation des femmes, avec ses recherches, ses tâtonnements et ses acquis importants.
Keywords: 1900-1999; amériques; anthologie; cours; fem1000; histoire et politique; militance; mouvements sociaux; mémoire collective; premier cycle; périodes historiques; québec; régions géographiques; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Femme, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques

Surpassing the love of men: Romantic friendship and love between women from the renaissance to the present. - Faderman, Lillian (W Morrow, 1981)
A classic of its kind, this fascinating cultural history draws on everything from private correspondence to pornography to explore five hundred years of friendship and love between women.Surpassing the Love of Men throws a new light on shifting theories of female sexuality and the changing status of women over the centuries.
Keywords: amitié; amour; approches et analyses; corps; droits des femmes*; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; phallocratie; ressource en ligne; sexualité; systèmes d'oppressions; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques

Visions partielles, visions partiales: visions des minoritaiers en sociologies - JUTEAU-LEE, Danielle (Sociologie et sociétés, 1981)
Résumé L'irruption du discours des minoritaires en sociologie fait éclater le discours des majoritaires en provoquant la remise en question de leurs explications à tendance naturaliste, culturaliste et psychologisante. Affichant le caractère partiel et partial de leurs visions, les femmes et les "ethniques" favorisent l'éclosion de synthèses provisoires, susceptibles de rendre compte des formes multiples de l'oppression
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; patriarcat; point de vue situé; pol4212; premier cycle; racisme; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; universalisme

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

Ce que veulent les femmes : articles et conférences de 1869 à 1891 - Deraismes, Maria (Mémoire des femmes, 1980)
Keywords: 1800-1899; conflit; cours; droits des femmes*; europe; fem1000; france; histoire et politique; militance; premier cycle; périodes historiques; régions géographiques; thématiques

Issue: social strategies by women artists - Lippard, Lucy R.; Institute of Contemporary Arts (Londres, Angleterre) (Institute of Contemporary Arts, 1980)
Catalogue for the exhibition Issue: social strategies by women artists, which took place in 1980 at the ICA, in London UK. Lucy Lippard, the exhibition’s organiser, described this as ‘the first establishment-approved women’s show in London’.36 She conceived it as ‘a framework for a transatlantic and cross-cultural dialogue’ about feminist art practice, and responses to various issues including ecology, unemployment, war and violence against women. The exhibition included many American women artists, including: Ariadne: A Social Art Network (Suzanne Lacy and Leslie Labowitz), Candace Hill-Montgomery, Jenny Holzer, Maria Karras, Mary Kelly, Margia Kramer, Beverly Naidus, Adrian Piper, Martha Rosler, Bonnie Sherk, Nancy Spero, May Stevens and Mierle Laderman Ukeles. Kelly, an American artist resident in England for many years, sensed that ‘in most of the work by American artists ... any emphasis on the “personal” appeared to detract from what they would consider “wider social issues”’.37 In this she distinguished it from European feminist work in which ‘the social and the psychic haven't been seen as necessarily antagonistic or contradictory’.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; royaume-uni; régions géographiques; sex1911; thématiques; états-unis

La noyante - Ouvrard, Hélène (Collection Littérature d'Amérique, 1980)
Ce roman pourrait être dédié aux gens qui ont encore "le courage de créer des traditions". L'auteure, comme l'écrit Madeleine Ouellette-Michalska, "articule la quête d'une liberté individuelle sur celle, plus vaste, d'un avenir collectif", en tentant une incursion dans la mythologie. Dans une antique demeure des bords du Richelieu, l'héroïne conjugue ses amours au féminin, et s'accepte Québécoise, c'est-à-dire divisée, avec "un oeil qui regrette l'Europe et l'autre qui convoite l'Amérique". Une oeuvre nationaliste et féministe. SDM.
Keywords: amériques; care; droits des femmes*; histoire et politique; nationalisme québécois; québec; roman; régions géographiques; thématiques; travail; travail domestique

The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting--Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz--and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Les femmes : caste, classe ou sexe opprimé - Reed, Evelyn (Féminisme et socialisme aux États-Unis. Textes du Parti socialiste des travailleurs, 1979)
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; classe sociale; cours; fem1000; histoire et politique; militance; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis

Women & art: a history of women painters and sculptors from the renaissance to the 20th century - Fine, Elsa Honig (Allanheld & Schram/Prior, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Histoire du feminisme français : du moyen âge à nos jours - Albistur, Maite; Armogathe, Daniel (Des femmes, 1977)
« Il s’agit de faire toute la lumière possible, en l’état actuel des connaissances, sur une protestation aussi ancienne que la pensée, mais régulièrement déjouée par les pièges de l’imaginaire masculin et du discours dominant. » Cette « querelle » des femmes a été analysée selon quatre temps forts : le temps du féminisme élitaire (du VIe siècle à 1789) ; une période de féminisme en mouvement (1789-1871) ; un temps de féminisme bourgeois et réformiste (1871-1945) ; enfin, une période de féminisme radical, inaugurée par Simone de Beauvoir dans Le Deuxième Sexe (1949). « C’est au total quinze siècles d’une autre histoire qui se déroulent sous nos yeux dans ces 500 pages d’analyse patiente, une histoire tour à tour sereine et passionnée, grave et légère, besogneuse et festive, une histoire arrachée aux pesanteurs des mythes, des doutes et de la mauvaise foi. » M.A. et D.A.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; approches et analyses; conditions des femmes*; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire du féminisme; histoire et politique; lit3220; moyen-âge; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Nos amis et nous. Les fondements cachés de quelques discours pseudo-féministes - Delphy, Christine (Questions Féministes, 1977)
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; inégalités; militance; patriarcat; premier cycle; pédagogie; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques

Mère de tant d'enfants - Obamsowin, Alanis (1977)
Dans son premier long métrage documentaire, sorti en 1977, Alanis Obomsawin rend hommage à la place centrale des femmes et des mères dans les cultures amérindiennes. Album de témoignages féminins autochtones, le film dépeint ces cultures matriarcales fortes, auxquelles on a tenté d'imposer pendant des siècles des habitudes et coutumes étrangères. Suivant le cycle de la vie des femmes autochtones de la naissance à la vieillesse en passant par l'enfance, la puberté, l'âge adulte et la maturité, il montre comment ces femmes se sont battues pour retrouver un sentiment d'égalité, inculquer la fierté de leur culture à leurs enfants et transmettre leurs histoires aux nouvelles générations.
Keywords: amériques; approches et analyses; cours; documentaire; fem3100; femmes* autochtones; histoire et politique; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

The Destruction of American Indian families - Unger, Steven (Association on American Indian Affairs, 1977)
Responding to the need for a comprehensive source of information regarding the separation of American Indian children from their families, this book presents essays which: examine the Indian child-welfare crisis in contemporary, legal, and historical perspectives; document the human cost of the crisis to Indian parents, children, and communities; and report on innovative programs designed and implemented by the Indian tribes themselves. Specifically, this book includes the following sections and essay titles: (1) Contemporary Overviews ("The Destruction of American Indian Families" and "The Role of the Federal Government: A Congressional View"); (2) Historical Perspectives ("The Effects of Boarding Schools on Indian Family Life: 1928" and "'Kid Catching' on the Navajo Reservation: 1920"); (3) The Human Cost ("'The Drunken Indian': Myths and Realities"; "The Wasted Strengths of Indian Families", "The Human Cost of Removing Indian Children from Their Families", "Child-Welfare Services to Indian People in the Albuquerque Area", "Indian Child Welfare in Oregon", "The Ravage of Indian Families in Crisis", "The Question of Best Interest", and "The Placement of American Indian Children--The Need for Change"); (4) A Legal Perspective ("Parent and Child Relationships in Law and in Navajo Custom"); (5) Tribal Actions ("Indian Children and Tribal Group Homes: New Interpretations of the Whipper Man" and "Tribal Resolutions"). (JC)
Keywords: american indian families; amériques; approches et analyses; autochtones; cours; discipline; droit; famille; his4443; histoire et politique; premier cycle; racisme; racisme systémique; residential schools; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques; violence coloniale; violence systémique; violences; états-unis

From the center: feminist essays on women's art - Lippard, Lucy R. (Dutton paperback original, 1976)
Lucy Lippard is both one of our finest critics of contemporary art and one of the most perceptive and strongest supporters of women artists. These thirty essays, written since the publication of Changing in 1971, delineate the growth of Lippard's feminism and the present status of women's art. In Lippards words: "...while I wish I could claim that this book established a new feminist criticism, all I can say is that it extends the basic knowledge of art by women, that it provides the raw material for such a development." From the Center is important, stimulating reading for all concerned with the women's art movement.
Keywords: 1900-1999; 1970-1979; amériques; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; théorie de l'art; états-unis

Women artists: recognition and reappraisal from the early Middle Ages to the twentieth century - Petersen, Karen; Wilson, J. J. (Harper colophon books ; CN 387, 1976)
Commentary on and photographs of sculpted and painted images of women created by women shed light upon feminine self-perceptions and the contributions of women artists through the centuries
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Conclusion. Conscience des femmes, monde de l'homme. - Rowbotham, Sheila (Conscience des femmes, monde de l'homme, 1976)
Dans la première partie de son essai, Sheila Rowbotham dit très concrètement à partir de son expérience personnelle, qui est aussi celle de toute la génération d’avant 1968, comment elle a pris conscience de son oppression et commencé à lutter. Du maquillage aux rêves, de la mode au militantisme, dans un monde créé par les hommes et pour l’homme, les femmes ont compris qu’elles étaient exclues, reléguées dans les rôles de mères et d’épouses, envers des rôles masculins dominants. Elle approfondit ensuite cette analyse dans la seconde partie en montrant la fonction particulière des rôles « féminins » dans le système capitaliste. Par le sous-paiement des emplois, le non-paiement du travail domestique et la reproduction qu’elles assurent, les femmes sont exploitées économiquement, idéologiquement et sexuellement. Et si cette situation prouve que le pouvoir capitaliste et le pouvoir masculins sont liés, c’est bien contre elle que les femmes se sont mises à lutter ensemble.
Keywords: 1900-1999; 1970-1979; approches et analyses; classe sociale; conflit; cours; division sexuelle du travail; fem1000; histoire et politique; militance; patriarcat; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; travail

Women painters of the world: from the time of Caterina Vigri, 1413-1463, to Rosa Bonheur and the present day - Sparrow, Walter Shaw (Hacker Art Books, 1976)
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques

Brouillon pour un dictionnaire des amantes - Wittig, Monique; Zeig, Sande (Grasset, 1976)
"Si vous manque l'imagination de ce que peuvent être les amantes dont parle ce Dictionnaire, il vous suffit d'y rechercher le terme. N'hésitez pas en recopier la définition comme je le fais ici : Les amantes sont celles qui, éprouvant un violent désir les unes pour les autres, vivent/aiment dans des peuples, suivant les vers de Sappho, "en beauté je chanterai mes amantes". Il serait difficile de faire plus clair, plus concis et plus élégant. Quelque chose pourtant vous chiffonne (vous constatez d'ailleurs que le mot "chiffon" est absent de ce dictionnaire) : la définition que vous venez de lire est subtilement circulaire et pleinement plurielle. Littré, Larousse, Robert ne procèdent pas ainsi : lexicographes positifs, ils nous enseignent entre autres choses positives, qu'une amante est une femme attachée à un homme par des sentiments tendres ; qu'au pluriel, le terme, dès lors nécessairement masculin (les amants) désigne un couple s'aimant d'amour réciproque. Or, les amantes de Wittig et Zeig vivent non en couples, mais en formation immédiatement politique (des peuples) et plurielle. Enfin, les amantes ne sont pas des femmes, et encore moins des femmes qui aiment des femmes. — Comment ça !? les amantes ne sont pas des femmes ?!
Keywords: amour lesbien; approches et analyses; discours dominant; histoire et politique; lesbianisme; personnes lesbiennes; sexisme; sexualité; systèmes d'oppressions; systéme hétérosexuel; thématiques

A history of women artists: [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present] - Munsterberg, Hugo (C. N. Potter : distributed by Crown Publishers, 1975)
A history of women artists : [Every art form-pottery, weaving, painting, graphics, sculpture, photography, from prehistoric times to the present]
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Pédagogie des opprimés suivi de Conscientisation et révolution - Freire, Paulo (Petite collection Maspero, 1974)
Ouvrage majeur de Paulo Freire, ce livre présente quelques aspects d’une pédagogie élaborée non seulement pour les opprimés, mais avec eux, et dans le cadre même de leur lutte perpétuelle pour affirmer leur humanité.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; inégalités; justice sociale; militance; pédagogie; ressource en ligne; systèmes d'oppressions; thématiques; éducation

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques

Un groupe de femmes de Montréal - Un groupe de femmes québécoises. (Manifeste des femmes québécoises, 1971)
Keywords: 1900-1999; 1970-1979; EDI; amériques; approches et analyses; conflit; cours; fem1000; groupes communautaires; histoire et politique; justice sociale; militance; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques

The politics of housework - Mainardi, Patricia; New England Free Press (New England Free Press, 1970)
Keywords: 1900-1999; 1970-1979; amérique du nord; amériques; approches et analyses; care; cours; discipline; féminisme marxiste; histoire et politique; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

Essays on sex equality. - Mill, John S.; Mill, Harriet H.; Rossi, Alice S. (The University of Chicago Press, 1970)
Ce volume rassemble pour la première fois tous les écrits de John Stuart Mill et Harriet Taylor Mill sur l'égalité entre les sexes, dont _The Subjection of Women_ de John Stuart Mill, un classique de l'histoire du mouvement des droits des femmes depuis sa publication il y a cent ans depuis. Ce volume contient également un important essai d'interprétation d'Alice S. Rossi sur Mill et Harriet Taylor qui décrit et analyse leur longue relation personnelle et intellectuelle.
Keywords: 1800-1899; EDI; approches et analyses; cours; fem1000; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; systèmes d'oppressions; thématiques

Sanaaq: roman - Nappaaluk, Mitiarjuk (Stanké, 1969)
« Sanaaq est le nom de l'héroine, dont on suit, tout au long du récit, les heurs et malheurs, avant et après l'arrivée des premiers Blancs en pays inuit. À l'image de Mitiarjuk, c'est une femme forte et équilibrée, sensible et déterminée, qui nous fait découvrir de l'intérieur, comme aucun Occidental, fût-il anthropologue, n'a encore pu le faire, la vie et la psychologie des Inuits confrontés à une nature extrême, à la nécessité du partage et à l'envahissement de leur territoire par les Blancs et leur civilisation. » -- Résumé de Publications Nunavik.
Keywords: 1900-1999; 1930-1939; 1940-1949; amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; littérature; littérature inuit; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires

Les guérillères - Wittig, Monique (Editions de Minuit, 1969)
Depuis qu'il y a des hommes et qu'ils pensent, ils ont chacun écrit l'histoire dans leur langage : au masculin. « Si les mots qualifiés sont de genres différents, l'adjectif se met au masculin pluriel » (Grévisse). Les Guérillères s'écrivent comme sujet collectif à la troisième personne du féminin pluriel. Dans les lacunes des textes magistraux qu'on nous a donnés à lire jusqu'ici, les bribes d'un autre texte apparaissent, le négatif ou plutôt l'envers des premiers, dévoilant soudain une force et une violence que de longs siècles d'oppression ont rendu explosives.
Keywords: approches et analyses; discours dominant; europe; france; histoire et politique; langage; littérature; patriarcat; poésie; régions géographiques; systèmes d'oppressions; thématiques

Sappho : histoire d'un poète et traduction intégrale de l'oeuvre - Mora, Édith (Flammarion, 1966)
Keywords: antiquité; approches et analyses; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Marie de l'Incarnation - Marie de l'Incarnation; Chabot, Marie-Emmanuel (Classiques canadiens, 1962)
Keywords: 1600-1699; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Le torrent - Hébert, Anne (Beauchemin, 1950)
Un enfant prisonnier de sa mère, au cœur d’un domaine bruissant d’eaux sauvages (Le torrent) ; un instant de tendresse dérisoire, qui change à jamais la vie sage d’une ouvrière-tricoteuse (La robe corail) ; l’exode vécu comme une fête par une petite serveuse, enfin libre au milieu des dangers (Le printemps de Catherine) ; la visite quotidienne d’un homme frustré à sa sœur, qu’il espère chaque jour trouver morte (La maison de l’esplanade)... Si divers que soient les paysages, les milieux, les situations, ces nouvelles d’Anne Hébert sont toutes tendues par une même force : celle de la passion (amour ou haine) qui saisit l’être dans les premiers temps de son existence, qui ne pourra être "dite" parce que la famille, la société ou la solitude refusent cette parole, et qui ne se délivrera d’elle-même que dans la mort — meurtre ou suicide. On retrouvera, à la mesure de ces thèmes, les qualités que "Les chambres de bois" et les "Poèmes" avaient révélées : sens concret de l’instant, vigueur et brièveté de l’écriture, saveur terrienne des images et des mots.
Keywords: 1900-1999; 1990-1999; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; maternité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études littéraires

Le deuxième sexe : l'expérience vécue - Beauvoir, Simone de (Gallimard, 1949)
Dans ce second volume, Simone de Beauvoir entreprend " d'étudier avec soin le destin traditionnel de la femme ", c'est à dire de " situer " la femme. " Comment la femme fait-elle l'apprentissage de sa condition, comment l'éprouve-t-elle, dans quel univers se trouve-t-elle enfermée, quelles évasions lui sont permises, voilà ce que je chercherai à décrire. " D'abord sa formation : dans l'enfance, dans l'adolescence, dans l'initiation sexuelle, tout semble disposé, agencé, pour creuser davantage le fossé naturel qui la sépare de l'homme, pour transformer des différences en inégalité, et cette inégalité en infériorité. Ensuite sa situation : Simone de Beauvoir décrit la femme dans le mariage, avec ses prémisses, ses traditions, ses conséquences ; dans la maternité ; dans la prostitution, dans la société ; dans le vieillissement et la vieillesse. Enfin elle envisage les problèmes qui se posent aux femmes qui " héritant d'un lourd passé, s'efforcent de forger un avenir nouveau "
Keywords: 1900-1999; 1940-1949; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; france; histoire et politique; incontournable; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sex3383; thématiques; écriture des femmes*

Le deuxième sexe : les faits et les mythes - Beauvoir, Simone de (Idées, 1949)
«Nous commencerons par discuter les points de vue pris sur la femme par la biologie, la psychanalyse, le matérialisme historique. Nous essaierons de montrer ensuite positivement comment la «réalité féminine» s'est constituée, pourquoi la femme a été définie comme l'Autre et quelles en ont été les conséquences du point de vue des hommes. Alors nous décrirons du point de vue des femmes le monde tel qu'il leur est proposé ; et nous pourrons comprendre à quelles difficultés elles se heurtent au moment où, essayant de s'évader de la sphère qui leur a été jusqu'à présent assignée, elles prétendent participer au mitsein humain». Simone de Beauvoir.
Keywords: 1900-1999; 1940-1949; cours; discipline; europe; fem1000; france; har4600; histoire et politique; incontournable; lit3220; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sex3383; thématiques; écriture des femmes*

L'oublié - Conan, Laure (Beauchemin, 1936)
Ce roman historique publié en 1900 est centré sur la fondation de Montréal. il a pour héros Lambert Closse. Il a été couronné par l'Académie française (Prix Montyon, 1902). Sources documentaires de l'auteur: l'«Histoire du Canada depuis sa découverte jusqu'à nos jours» de F. X. Garneau et les «Relations des Jésuites». [SDM].
Keywords: 1600-1699; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; premier cycle; périodes historiques; québec; roman; régions géographiques; thématiques; études littéraires